Forms and compositions of sodium chenodeoxycholate

By developing bilayer tablets and polycrystalline solid preparations, the problems of side effects of abdominal pain and spasm in IBS-C treatment were solved, and more effective therapeutic effects and release control were achieved.

CN119213007APending Publication Date: 2024-12-27SYNTIS BIO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040160.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-03-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing sodium von deoxycholate (NaCDC) preparations still have abdominal pain and spastic side effects in the treatment of constipation irritable bowel syndrome (IBS-C), and due to the high local concentrations when released in the intestine, The decrease in colon water content makes it challenging to release controlled release systems.

Method used

Develop a double-layer tablet containing sodium ges deoxycholate, using a coating structure of an instant and sustained release layer, reducing the incidence of large-scale shrinkage through improved coating technology, and providing polycrystalline solid form for improved stability sex and bioavailability.

Benefits of technology

It effectively reduces the incidence of abdominal pain and spasm, improves the therapeutic effect, and solves the problems of release control and stability through improved solid form and coating technology, providing a more effective treatment plan for gastrointestinal diseases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213007A_ABST
    Figure CN119213007A_ABST
Patent Text Reader

Abstract

The present disclosure provides solid forms of sodium chenodeoxycholate (NaCDC) as well as compositions thereof, and methods of use and preparation thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority to and the benefit of Italian Application No. 102022000006161, filed on March 29, 2022, and Italian Application No. 102022000019725, filed on September 26, 2022, the entire contents of each of which are hereby incorporated by reference. Background Art

[0003] Chenodeoxycholic acid (CDCA) is a bile acid that has been used as a therapy, including, for example, for patients with gallstones, although a side effect is diarrhea. Additionally, sodium chenodeoxycholate (NaCDC) has been studied for use as a treatment for constipation. See, e.g., Rao, AS et al., Gastroenterology, 2010 Nov; 139(5): 1549-1558.e.1. Summary of the invention

[0004] The present disclosure recognizes the need for new formulations of chenodeoxycholic acid (CDCA) or its salts and provides such formulations and related technologies (eg, methods, compositions, etc.).

[0005] Specifically, although formulations containing CDCA salts (sodium chenodeoxycholate, NaCDC) in Eudragit S100 coated capsules showed effective treatment of symptoms of irritable bowel syndrome with constipation (IBS-C), nearly half of patients suffered from abdominal pain and cramping. See Rao, AS et al., Gastroenterology, November 2010; 139(5): 1549-1558.e.1. Steiger et al. hypothesized that such side effects may be driven by higher local concentrations of chenodeoxycholate (CDC) when released in the intestine, but further recognized that it may be challenging to effectively release CDC from a controlled release system due to reduced water content along the colon. Therefore, they preliminarily evaluated a coated bilayer tablet formulation comprising an immediate-release layer and a sustained-release layer and demonstrated a promising in vitro release pattern and a reduced incidence of large-scale contractions when tablets were administered to the pig rectum. See Steiger, C. et al., Clin. Transl. Gastroenterology 2020; 11: e00229. The present disclosure provides insight that the development of formulations comprising CDCA or its salts remains an important aspect in establishing new treatments for gastrointestinal disorders such as IBS-C.

[0006] The present disclosure provides solid forms of sodium chenodeoxycholate (NaCDC) and compositions thereof and use and preparation methods thereof and technologies related thereto. In some embodiments, the solid forms provided can be used to treat gastrointestinal disorders, such as constipation (e.g., IBS-C). In some embodiments, the solid forms provided can be used to prepare new NaCDC preparations, such as preparations specifically designed to solve certain problems of previous CDCA or its salt preparations. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 is the X-ray powder diffraction (XRPD) pattern of NaCDC Form A.

[0008] Figure 2 is the differential scanning calorimetry (DSC) curve of NaCDC Form A.

[0009] Figure 3 is the thermogravimetric analysis (TGA) curve of NaCDC Form A.

[0010] Figure 4 is a series of XRPD patterns showing NaCDC Form A before (bold lines) and after (thin lines) exposure to RH 95% for 15 hours at room temperature.

[0011] Figure 5 is the X-ray powder diffraction (XRPD) pattern of NaCDC Form B.

[0012] Figure 6 is the differential scanning calorimetry (DSC) curve of NaCDC Form B.

[0013] Figure 7 is the thermogravimetric analysis (TGA) curve of NaCDC Form B.

[0014] Figure 8 is a series of XRPD patterns showing NaCDC Form B before (bold lines) and after (thin lines) exposure to RH 95% for 15 hours at room temperature.

[0015] Fig. 9 is a dynamic vapor sorption (DVS) graph of NaCDC Form A.

[0016] Fig.10 This is the DVS diagram of NaCDC form B.

[0017] Fig.11 The intrinsic dissolution profiles of NaCDC Form A and NaCDC Form B are shown.

[0018] Fig.12 Linear regression analysis of the intrinsic dissolution profiles of NaCDC Form A and NaCDC Form B is shown.

[0019] Fig.13 Solubility curves of NaCDC Form A and NaCDC Form B are shown.

[0020] Fig.14 This is the DSC curve of NaCDC Form B.

[0021] Fig.15 TG (top) / DSC (bottom) analysis of NaCDC Form B.

[0022] Fig.16 is a series of XRPD patterns showing the material obtained after heating NaCDC Form B at 315°C (bottom) and 360°C (top).

[0023] Fig.17 is a series of XRPD patterns showing the material obtained after exposure of NaCDC Form B to 254 nm UV light under various conditions. From bottom to top: starting material; clear vial; amber vial; control.

[0024] Fig.18 is a series of XRPD patterns showing NaCDC Form B (bottom) and material obtained from experiments ST19 (middle) and ST20 (top).

[0025] Fig.19A is the XRPD pattern of Form S1 obtained from experiment ST19.

[0026] Fig.19B is a TG (top) / DSC (bottom) analysis chart of Form S1.

[0027] Fig. 20 is a series of XRPD patterns obtained from some solubility experiments. From bottom to top: NaCDC Form B; NaCDC Form B after heating at 315°C; ST19; SAS03; SAS07; SAS08; SAS24; SAS33; SAS39; SAS46; SAS47; and SAS48.

[0028] Fig.21A is a TG (top) / DSC (bottom) analysis graph of Form S2.

[0029] Fig. 21B is the XRPD pattern of Form S3 obtained from experiment SAS07.

[0030] Fig. 22 is a TG (top) / DSC (bottom) analysis graph of Form S4.

[0031] Fig.23Ais a series of XRPD patterns showing material obtained from experiments SAS47 (bottom) and FAS08 (top).

[0032] Fig. 23B is a TG (top) / DSC (bottom) analysis graph of Form S5.

[0033] Fig.24A is a series of XRPD patterns showing material obtained from experiments ST19, SL13, SL39 and RAS11 (from bottom to top).

[0034] Fig. 24B is a TG (top) / DSC (bottom) analysis chart of Form S1 (or a form similar to and / or isostructural to Form S1).

[0035] Fig.25 is a TG (top) / DSC (bottom) analysis graph of Form S2.

[0036] Fig.26A is a series of XRPD patterns showing material obtained from experiments SL27 (bottom) and SL56 (top).

[0037] Fig.26B is a TG (top) / DSC (bottom) analysis graph of Form S7.

[0038] Fig. 27 is a TG (top) / DSC (bottom) analysis chart of Form S1 (or a form similar to and / or isostructural to Form S1).

[0039] Fig.28 is a TG (top) / DSC (bottom) analysis graph of Form S5.

[0040] Fig.29 is a TG (top) / DSC (bottom) analysis graph of Form S6.

[0041] Fig.30 is a TG (top) / DSC (bottom) analysis graph of Form S2.

[0042] Fig.31A is the XRPD pattern of Form S4.

[0043] Fig.31B is a TG (top) / DSC (bottom) analysis graph of Form S4.

[0044] Fig.32A is a TG (top) / DSC (bottom) analysis graph of Form S5.

[0045] Fig.32B is a TG (top) / DSC (bottom) analysis graph of Form S5.

[0046] Fig.33 is the XRPD pattern of Form S2.

[0047] Fig.34A is a series of XRPD patterns showing material obtained from experiment VDS012 (top) and NaCDC Form B (bottom).

[0048] Fig.34B is a TG (top) / DSC (bottom) analysis graph of Form S8.

[0049] Fig.35 is a series of XRPD patterns showing material obtained from experiments ASDS17, ASDS21, ST19, ASDS03, ASDS03 stored for about three weeks, and SDGR03 (bottom to top).

[0050] Fig.36 is a TG (top) / DSC (bottom) analysis graph of Form S14.

[0051] Fig.37 is a series of XRPD patterns showing material obtained from experiments ASDS04, ASDS04 stored for 22 days, ASDS08 stored for 23 days, NaCDC monohydrate, ASDS08, and NaCDC hemihydrate (bottom to top).

[0052] Fig.38 TG (top) / DSC (bottom) analysis of Form S9-a obtained from a sample stored for 22 days in Experiment ASDS04.

[0053] Fig.39 TG (top) / DSC (bottom) analysis of Form S9-a obtained from a sample stored for 23 days in Experiment ASDS08.

[0054] Fig.40A is the XRPD spectrum of Form S10.

[0055] Fig.40B is a TG (top) / DSC (bottom) analysis graph of Form S10.

[0056] Fig.41 TG (top) / DSC (bottom) analysis chart of Form S11.

[0057] Fig.42 is a series of XRPD patterns showing material obtained from experiment ASDS19 (bottom), a sample from experiment ASDS19 that had been stored for 22 days (middle), and experiment RAS36.

[0058] Fig.43is a TG (top) / DSC (bottom) analysis graph of Form S12.

[0059] Fig.44 is a series of XRPD patterns showing material obtained from experiment ASDS16 before (bottom) and after (top) storage for 22 days.

[0060] Fig.45 is a TG (top) / DSC (bottom) analysis graph of Form S13.

[0061] Fig.46A is the XRPD spectrum of Form S14.

[0062] Fig.46B is a TG (top) / DSC (bottom) analysis graph of Form S14.

[0063] Fig.47 is a TG (top) / DSC (bottom) analysis graph of Form S5.

[0064] Fig.48 is a series of XRPD patterns showing material obtained from Experiment RAS11 before (bottom) and after (top) storage at RT for two weeks.

[0065] Fig.49 is a TG (top) / DSC (bottom) analysis chart of Form S1 (or a form similar to and / or isostructural to Form S1).

[0066] Fig.50A is a series of XRPD patterns showing material obtained from experiments SAS07, RAS34, RAS33 and ASDS18 (bottom to top).

[0067] Fig.50B is a TG (top) / DSC (bottom) analysis graph of Form S3 (or a form similar to and / or isostructural to Form S3).

[0068] Fig.51 is a series of XRPD patterns showing material obtained from experiment RAS33 before (bottom) and after (middle) storage at RT for two weeks, and Form S1 (top - obtained from experiment RAS11).

[0069] Fig.52 is a TG (top) / DSC (bottom) analysis graph of Form S6 (or a form similar to and / or isostructural to Form S6).

[0070] Fig.53 is the XRPD pattern of the material obtained from experiment RAS037.

[0071] Fig.54Ais a series of XRPD patterns showing material obtained from Experiment RAS36 before (bottom) and after (middle) storage in solution at RT for two weeks, and Form S14 (top - obtained from Experiment ASDS17).

[0072] Fig.54B TG (top) / DSC (bottom) analysis of the material after two weeks storage at RT obtained from experiment RAS36. DETAILED DESCRIPTION

[0073] Chenodeoxycholic acid

[0074] Chenodeoxycholic acid (CDCA) is a bile acid with the following structure:

[0075] CDCA

[0076] There remains a need to identify salts and / or solid forms of CDCA that can be used for various therapeutic applications, such as those described herein. It would be desirable to provide a form (e.g., salt and / or solid form) of CDCA that imparts characteristics such as improved stability, solubility, hygroscopicity (e.g., a provided form may be less hygroscopic than another form), bioavailability, pharmacokinetics, and / or ease of formulation compared to another form (e.g., an amorphous form) of CDCA.

[0077] Sodium chenodeoxycholate

[0078] In some embodiments, the present disclosure provides a salt form of CDCA (e.g., a sodium salt form of CDCA, also known as sodium chenodeoxycholate or NaCDC). In some embodiments, the present disclosure provides a crystalline solid form of sodium chenodeoxycholate (NaCDC). In some embodiments, the present disclosure provides one or more polymorphic solid forms of NaCDC. As used herein, the term "polymorph" refers to the ability of a compound to exist in one or more different crystal structures. For example, one or more polymorphs may vary in pharmaceutically relevant physical properties (e.g., solubility, stability, and / or hygroscopicity) between one form and another.

[0079] It should be understood that the crystalline solid form of NaCDC can exist in pure or non-solvated form, hydrated form, solvated form and / or heterosolvated form. In some embodiments, the crystalline solid form of NaCDC does not have any water or solvent incorporated into the crystalline structure (i.e., "unsolvated" or "anhydrate"). In some embodiments, the crystalline solid form of NaCDC contains water and / or solvent in the crystalline structure (i.e., hydrate and / or solvate, respectively). As used herein, the term "solvate" refers to a solid form in which a stoichiometric or non-stoichiometric amount of one or more solvents are incorporated into the crystal structure. For example, a solvated or heterosolvated polymorph may independently include 0.05, 0.1, 0.2, 0.5, 1.0, 1.5, 2.0 equivalents of one or more solvents incorporated into the crystal lattice. As used herein, the term "hydrate" refers to a solvate in which the solvent incorporated into the crystal structure is water. It should be understood that solvates containing only certain solvents (most notably water) are suitable for development as drugs. See Zhang, C. et al., J. Pharm. Sci., 2018, 107(10): 2731-34. Solvates containing other solvents are particularly useful in manufacturing and / or testing, even though they may not be acceptable for use in approved drug products.

[0080] In some embodiments, the present disclosure provides NaCDC as a hydrate (eg, a sesquihydrate). In some embodiments, the present disclosure provides NaCDC as an anhydrate.

[0081] In some embodiments, the present disclosure provides NaCDC as a solvate (e.g., a solvate of ethanol, ethyl acetate, methanol, methyl tert-butyl ether, trifluoroethanol, or water, or any combination thereof).

[0082] It should be further understood that the term "salt" or "salt form" encompasses complexes of CDCA with an acid or base, including those resulting from ionic interactions between CDCA and an acid or base, and non-ionic associations between CDCA and a neutral substance. In some embodiments, a salt form is provided resulting from an ionic interaction between CDCA and a base (e.g., a sodium base, such that the resulting form is NaCDC).

[0083] As used herein, the term "about" when used in reference to a degree 2-theta value refers to the stated value ± 0.2 degrees 2-theta. In other embodiments, the degree 2-theta values ​​provided refer to the stated value ± 0.1 degrees 2-theta.

[0084] Form A

[0085] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form A. In some embodiments, Form A is a hydrate (eg, a sesquihydrate).

[0086] In some embodiments, Form A is characterized in that one or more peaks in its XRPD pattern are selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ. In some embodiments, Form A is characterized in that two or more peaks in its XRPD pattern are selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ. In some embodiments, Form A is characterized in that three or more peaks in its XRPD pattern are selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ. In some embodiments, Form A is characterized in that four or more peaks in its XRPD pattern are selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ. In some embodiments, Form A is characterized in that five or more peaks in its XRPD pattern are selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ. In some embodiments, Form A is characterized in that six or more peaks in its XRPD pattern are selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ.

[0087] In some embodiments, Form A is characterized by peaks in its XRPD pattern selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-theta. In some embodiments, Form A is characterized by peaks in its XRPD pattern located at substantially all of the following positions:

[0088]

[0089]

[0090] In some embodiments, Form A is characterized by one or more of the following:

[0091] (i) Basically similar to Figure 1 The XRPD pattern depicted in;

[0092] (ii) DSC graph showing water loss starting from slightly above ambient temperature and continuing to about 150°C;

[0093] (iii) substantially similar to Figure 2 The DSC diagram depicted in ;

[0094] (iv) a TGA graph showing a weight loss of 4.3% up to 150°C; and

[0095] (v) Basically similar to Figure 3 TGA diagram depicted in .

[0096] Form B

[0097] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form B. In some embodiments, Form B is an anhydrate.

[0098] In some embodiments, Form B is characterized by one or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-θ. In some embodiments, Form B is characterized by two or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-θ. In some embodiments, Form B is characterized by three or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-θ. In some embodiments, Form B is characterized by four or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-theta. In some embodiments, Form B is characterized by five or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-theta.

[0099] In some embodiments, Form B is characterized by peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-theta. In some embodiments, Form B is characterized by peaks in its XRPD pattern located at substantially all of the following positions:

[0100] 2θ±0.2[°] 6.75 8.14 9.79 11.33 13.27 13.56 14.02 14.79 15.05 16.10 16.37 16.78 17.74 18.63 19.71 20.00 20.35 21.89 22.90

[0101] In some embodiments, Form B is characterized by one or more of the following:

[0102] (i) Basically similar to Figure 5 The XRPD pattern depicted in;

[0103] (ii) DSC graph showing no thermal events from room temperature to about 288°C;

[0104] (iii) substantially similar to Figure 6 The DSC diagram depicted in ;

[0105] (iv) a TGA graph showing a weight loss of <0.1% up to 150°C; and

[0106] (v) Basically similar to Figure 7 TGA diagram depicted in .

[0107] In some embodiments, Form B is characterized by one or more of the following:

[0108] (i) Basically similar to Figure 5 The XRPD pattern depicted in;

[0109] (ii) DSC graph showing no thermal events from room temperature to about 288°C;

[0110] (iii) substantially similar to Figure 6 The DSC diagram depicted in ;

[0111] (iv) TGA graph showing weight loss <0.1% up to 150°C;

[0112] (v) Basically similar to Figure 7 The TGA diagram depicted in ;

[0113] (vi) Basically similar to Fig.14 The DSC diagram depicted in ;

[0114] (vii) substantially similar to Fig.15 The TGA graph depicted in ; and

[0115] (viii) is basically similar to Fig.15 DSC diagram depicted in .

[0116] Form S1

[0117] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S1. In some embodiments, Form S1 is a solvate. In some embodiments, Form S1 is a methyl ethyl ketone solvate. In some embodiments, Form S1 is a methyl tert-butyl ether solvate. In some embodiments, Form S1 is a trifluoroethanol solvate. In some embodiments, Form S1 is an acetone solvate. In some embodiments, Form S1 is a hydrate.

[0118] In some embodiments, "Form S1" refers to one or more similar and / or isostructural forms characterized by the properties described herein.

[0119] In some embodiments, Form S1 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ. In some embodiments, Form S1 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ. In some embodiments, Form S1 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ. In some embodiments, Form S1 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ. In some embodiments, Form S1 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ. In some embodiments, Form S1 is characterized in that six or more peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ.

[0120] In some embodiments, Form S1 is characterized in that the peaks in its XRPD pattern are selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ. In some embodiments, Form S1 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S1-A. In some embodiments, Form S1 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S1-B.

[0121] In some embodiments, Form S1 is characterized by one or more of the following:

[0122] (i) Basically similar to Fig.19A , Fig.24A and / or Fig.48 The XRPD pattern depicted in;

[0123] (ii) a DSC plot showing thermal events at about 96.0°C, about 142.5°C, and / or about 313.4°C;

[0124] (iii) substantially similar to Fig.19B , Fig. 24B , Fig. 27 and / or Fig.49 The DSC diagram depicted in ;

[0125] (iv) a TGA graph showing a weight loss of about 2.177% up to about 150°C; and

[0126] (v) Basically similar to Fig.19B , Fig. 24B , Fig. 27 and / or Fig.49 TGA diagram depicted in .

[0127] Form S2

[0128] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S2. In some embodiments, Form S2 is a solvate. In some embodiments, Form S2 is an ethanol solvate.

[0129] In some embodiments, Form S2 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-θ. In some embodiments, Form S2 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-θ. In some embodiments, Form S2 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-θ. In some embodiments, Form S2 is characterized by four or more peaks in its XRPD pattern selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-θ. In some embodiments, Form S2 is characterized by five or more peaks in its XRPD pattern selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-θ.

[0130] In some embodiments, Form S2 is characterized in that the peaks in its XRPD pattern are selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-θ. In some embodiments, Form S2 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S2.

[0131] In some embodiments, Form S2 is characterized by one or more of the following:

[0132] (i) Basically similar to Fig.33 The XRPD pattern depicted in;

[0133] (ii) a DSC graph showing thermal events at about 112.9°C, about 177.8°C, and / or about 334.1°C;

[0134] (iii) substantially similar to Fig.21A , Fig.25 and / or Fig.30 The DSC diagram depicted in ;

[0135] (iv) a TGA graph showing a weight loss of about 3.95% up to about 150°C; and

[0136] (v) Basically similar to Fig.21A , Fig.25 and / or Fig.30 TGA diagram depicted in .

[0137] Form S3, Form S6 and Form S11

[0138] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S3, Form S6 and / or Form S11. In some embodiments, Form S3 and / or Form S11 is an anhydrate. In some embodiments, Form S6 is a solvate. In some embodiments, Form S6 is an ethyl acetate solvate. In some embodiments, Form S3, Form S6 and Form S11 are similar and / or isostructural to each other. Therefore, in some embodiments, Form S3, Form S6 and / or Form S11 share one or more characteristics described herein.

[0139] In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-θ. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-θ. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-θ. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-θ. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-θ.

[0140] In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that the peaks in its XRPD pattern are selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-θ. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S3. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S6. In some embodiments, Form S3, Form S6, and / or Form S11 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S11.

[0141] In some embodiments, Form S3, Form S6, and / or Form S11 are characterized by one or more of the following:

[0142] (i) Basically similar to Fig. 21B and / or Fig.50A The XRPD pattern depicted in;

[0143] (ii) a DSC plot showing thermal events at about 50.6°C, about 199.8°C, and / or about 331.5°C;

[0144] (iii) substantially similar to Fig.29 and / or Fig.41 The DSC diagram depicted in ;

[0145] (iv) a TGA graph showing a weight loss of about 2.456% up to about 150°C; and

[0146] (v) Basically similar to Fig.29 and / or Fig.41 TGA diagram depicted in .

[0147] Form S4

[0148] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S4. In some embodiments, Form S4 is a solvate. In some embodiments, Form S4 is a 2,2,2-trifluoroethanol (TFE) solvate.

[0149] In some embodiments, Form S4 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ. In some embodiments, Form S4 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ. In some embodiments, Form S4 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ. In some embodiments, Form S4 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ. In some embodiments, Form S4 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ. In some embodiments, Form S4 is characterized in that six or more peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ.

[0150] In some embodiments, Form S4 is characterized in that the peaks in its XRPD pattern are selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ. In some embodiments, Form S4 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S4.

[0151] In some embodiments, Form S4 is characterized by one or more of the following:

[0152] (i) Basically similar to Fig.31A The XRPD pattern depicted in;

[0153] (ii) a DSC graph showing thermal events at about 146.5°C and / or about 333.9°C;

[0154] (iii) substantially similar to Fig. 22 and / or Fig.31B The DSC diagram depicted in ;

[0155] (iv) a TGA graph showing a weight loss of about 14.23% up to about 180°C; and

[0156] (v) Basically similar to Fig. 22 and / or Fig.31B TGA diagram depicted in .

[0157] Form S5

[0158] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S5. In some embodiments, Form S5 is a solvate. In some embodiments, Form S5 is a methanol solvate.

[0159] In some embodiments, Form S5 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ. In some embodiments, Form S5 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ. In some embodiments, Form S5 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ. In some embodiments, Form S5 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ. In some embodiments, Form S5 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ. In some embodiments, Form S5 is characterized in that six or more peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ.

[0160] In some embodiments, Form S5 is characterized in that the peaks in its XRPD pattern are selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-θ. In some embodiments, Form S5 is characterized in that the peaks in its XRPD pattern are located at substantially all of the positions listed in Table S5-A. In some embodiments, Form S5 is characterized in that the peaks in its XRPD pattern are located at substantially all of the positions listed in Table S5-B.

[0161] In some embodiments, Form S5 is characterized by one or more of the following:

[0162] (i) Basically similar to Fig.23A The XRPD pattern depicted in;

[0163] (ii) a DSC graph showing thermal events at about 82°C, about 183.9°C, and / or about 331.5°C;

[0164] (iii) substantially similar to Fig. 23B , Fig.28 , Fig.32A , Fig.32B and / or Fig.47 The DSC diagram depicted in ;

[0165] (iv) a TGA graph showing a weight loss of about 4.79% up to about 180°C; and

[0166] (v) Basically similar to Fig. 23B , Fig.28 , Fig.32A , Fig.32B and / or Fig.47 TGA diagram depicted in .

[0167] Form S7

[0168] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S7. In some embodiments, Form S7 is a solvate. In some embodiments, Form S7 is an isopropanol solvate.

[0169] In some embodiments, Form S7 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-θ. In some embodiments, Form S7 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-θ. In some embodiments, Form S7 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-θ. In some embodiments, Form S7 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-θ. In some embodiments, Form S7 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-θ.

[0170] In some embodiments, Form S7 is characterized in that the peaks in its XRPD pattern are selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-θ. In some embodiments, Form S7 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S7.

[0171] In some embodiments, Form S7 is characterized by one or more of the following:

[0172] (i) Basically similar to Fig.26A The XRPD pattern depicted in;

[0173] (ii) a DSC graph showing thermal events at about 109.2°C, about 324.5°C, and / or about 335.3°C;

[0174] (iii) substantially similar to Fig.26B The DSC diagram depicted in ;

[0175] (iv) a TGA graph showing a weight loss of about 10.04% up to about 180°C; and

[0176] (v) Basically similar to Fig.26B TGA diagram depicted in .

[0177] Form S9-a

[0178] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S9-a. In some embodiments, Form S9-a is a solvate. In some embodiments, Form S9-a is a solvate of acetonitrile, water, or a combination thereof.

[0179] In some embodiments, Form S9-a is characterized in that one or more peaks in its XRPD pattern are selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-θ. In some embodiments, Form S9-a is characterized in that two or more peaks in its XRPD pattern are selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-θ. In some embodiments, Form S9-a is characterized in that three or more peaks in its XRPD pattern are selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-θ. In some embodiments, Form S9-a is characterized in that four or more peaks in its XRPD pattern are selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-θ. In some embodiments, Form S9-a is characterized in that five or more peaks in its XRPD pattern are selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-θ.

[0180] In some embodiments, Form S9-a is characterized in that the peaks in its XRPD pattern are selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-θ. In some embodiments, Form S9-a is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S9-a.

[0181] In some embodiments, Form S9-a is characterized by one or more of the following:

[0182] (i) Basically similar to Fig.37 The XRPD pattern depicted in (bottom spectrum);

[0183] (ii) a DSC graph showing thermal events at about 99.9° C. and / or about 328° C.;

[0184] (iii) substantially similar to Fig.38 and / or Fig.39 The DSC diagram depicted in ;

[0185] (iv) a TGA graph showing a weight loss of about 8.635% up to about 150°C; and

[0186] (v) Basically similar to Fig.38 and / or Fig.39 TGA diagram depicted in .

[0187] Form S9-b

[0188] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S9-b.

[0189] In some embodiments, form S9-b is characterized in that one or more peaks in its XRPD pattern are selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-θ. In some embodiments, form S9-b is characterized in that two or more peaks in its XRPD pattern are selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-θ. In some embodiments, form S9-b is characterized in that three or more peaks in its XRPD pattern are selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-θ. In some embodiments, form S9-b is characterized in that four or more peaks in its XRPD pattern are selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-θ. In some embodiments, Form S9-b is characterized by five or more peaks in its XRPD pattern selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-theta.

[0190] In some embodiments, Form S9-b is characterized in that the peaks in its XRPD pattern are selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-theta. In some embodiments, Form S9-b is characterized in that the peaks in its XRPD pattern are located at substantially all of the positions listed in Table S9-b. In some embodiments, Form S9-b is characterized in that it is substantially similar to Fig.37 (second spectrum from the top).

[0191] Form S10

[0192] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S10. In some embodiments, Form S10 is a solvate. In some embodiments, Form S10 is a solvate of 2,2,2-trifluoroethanol (TFE), ethyl acetate, or a combination thereof.

[0193] In some embodiments, Form S10 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ. In some embodiments, Form S10 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ. In some embodiments, Form S10 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ. In some embodiments, Form S10 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ. In some embodiments, Form S10 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ. In some embodiments, Form S10 is characterized in that six or more peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ.

[0194] In some embodiments, Form S10 is characterized in that the peaks in its XRPD pattern are selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-θ. In some embodiments, Form S10 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S10.

[0195] In some embodiments, Form S10 is characterized by one or more of the following:

[0196] (i) Basically similar to Fig.40A The XRPD pattern depicted in;

[0197] (ii) a DSC graph showing thermal events at about 141.3° C., about 324° C., and / or about 336° C.;

[0198] (iii) substantially similar to Fig.40B The DSC diagram depicted in ;

[0199] (iv) a TGA graph showing a weight loss of about 16% up to about 150°C; and

[0200] (v) Basically similar to Fig.40B TGA diagram depicted in .

[0201] Form S12 and Form S15

[0202] In some embodiments, the present disclosure provides sodium chenodeoxycholate as form S12 and / or form S15. In some embodiments, form S12 and / or form S15 are solvates. In some embodiments, form S12 and / or form S15 are methyl tert-butyl ether (MTBE) solvates. In some embodiments, form S12 and form S15 are similar and / or isostructural to each other. Therefore, in some embodiments, form S12 and / or form S15 share one or more characteristics described herein.

[0203] In some embodiments, Form S12 and / or Form S15 are characterized in that one or more peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ. In some embodiments, Form S12 and / or Form S15 are characterized in that two or more peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ. In some embodiments, Form S12 and / or Form S15 are characterized in that three or more peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ. In some embodiments, form S12 and / or form S15 are characterized in that four or more peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ. In some embodiments, form S12 and / or form S15 are characterized in that five or more peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ. In some embodiments, form S12 and / or form S15 are characterized in that six or more peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ.

[0204] In some embodiments, Form S12 and / or Form S15 are characterized in that the peaks in their XRPD patterns are selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-θ. In some embodiments, Form S12 and / or Form S15 are characterized in that the peaks in their XRPD patterns are located at substantially all positions listed in Table S12. In some embodiments, Form S12 and / or Form S15 are characterized in that the peaks in their XRPD patterns are located at substantially all positions listed in Table S15.

[0205] In some embodiments, Form S12 and / or Form S15 are characterized by one or more of the following:

[0206] (i) Basically similar to Fig.42 The XRPD pattern depicted in;

[0207] (ii) a DSC graph showing thermal events at about 80.8°C, about 180°C, and / or about 332°C;

[0208] (iii) substantially similar to Fig.43 The DSC diagram depicted in ;

[0209] (iv) a TGA graph showing a weight loss of about 4.448% up to about 150°C; and

[0210] (v) Basically similar to Fig.43 TGA diagram depicted in .

[0211] Form S13

[0212] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S13. In some embodiments, Form S13 is a solvate. In some embodiments, Form S13 is a solvate of 2,2,2-trifluoroethanol (TFE), diisopropyl ether, or a mixture thereof.

[0213] In some embodiments, Form S13 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-θ. In some embodiments, Form S14 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-θ. In some embodiments, Form S14 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-θ. In some embodiments, Form S14 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-θ. In some embodiments, Form S14 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-θ.

[0214] In some embodiments, Form S13 is characterized in that the peaks in its XRPD pattern are selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-θ. In some embodiments, Form S13 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S13.

[0215] In some embodiments, Form S13 is characterized by one or more of the following:

[0216] (i) Basically similar to Fig.44 and / or Fig.53 The XRPD pattern depicted in;

[0217] (ii) a DSC graph showing thermal events at about 55.4°C, about 148.8°C, about 191.8°C, and / or about 335°C;

[0218] (iii) substantially similar to Fig.45 The DSC diagram depicted in ;

[0219] (iv) a TGA graph showing a weight loss of about 6.162% up to about 180°C; and

[0220] (v) Basically similar to Fig.45 TGA diagram depicted in .

[0221] Form S14

[0222] In some embodiments, the present disclosure provides sodium chenodeoxycholate as Form S14. In some embodiments, Form S14 is a solvate. In some embodiments, Form S14 is a 2,2,2-trifluoroethanol (TFE) solvate.

[0223] In some embodiments, Form S14 is characterized in that one or more peaks in its XRPD pattern are selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-θ. In some embodiments, Form S14 is characterized in that two or more peaks in its XRPD pattern are selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-θ. In some embodiments, Form S14 is characterized in that three or more peaks in its XRPD pattern are selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-θ. In some embodiments, Form S14 is characterized in that four or more peaks in its XRPD pattern are selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-θ. In some embodiments, Form S14 is characterized in that five or more peaks in its XRPD pattern are selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-θ.

[0224] In some embodiments, Form S14 is characterized in that the peaks in its XRPD pattern are selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-θ. In some embodiments, Form S14 is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S14.

[0225] In some embodiments, Form S14 is characterized by one or more of the following:

[0226] (i) Basically similar to Fig.46A The XRPD pattern depicted in;

[0227] (ii) a DSC graph showing thermal events at about 143.7° C. and / or about 331° C.;

[0228] (iii) substantially similar to Fig.46B The DSC diagram depicted in ;

[0229] (iv) a TGA graph showing a weight loss of about 15.84% up to about 180°C; and

[0230] (v) Basically similar to Fig.46B TGA diagram depicted in .

[0231] Preparation of the solid form provided

[0232] In some embodiments, the present disclosure provides methods of preparing a crystalline solid form of sodium chenodeoxycholate (NaCDC).

[0233] In some embodiments, the solid form of NaCDC is prepared by contacting CDCA (e.g., amorphous CDCA, crystalline CDCA, or a mixture thereof) with a suitable base (such as sodium hydroxide). In some embodiments, the present disclosure provides a method for preparing NaCDC, comprising the steps of: providing CDCA; and optionally combining CDCA with a suitable base (e.g., sodium hydroxide) in a suitable solvent to provide NaCDC. In some embodiments, about 1.0, about 2.0, about 3.0, about 4.0, about 5.0 or more equivalents of a suitable base (e.g., sodium hydroxide) are added.

[0234] In some embodiments, the solid form of NaCDC is prepared by dissolving NaCDC (e.g., amorphous NaCDC, crystalline NaCDC, or a mixture thereof) in a suitable solvent, and then causing NaCDC to return to a solid phase. In some embodiments, the solid form of NaCDC is prepared by combining NaCDC (e.g., amorphous NaCDC, crystalline NaCDC, or a mixture thereof) in a suitable solvent under suitable conditions and separating the solid form of NaCDC. In some embodiments, the solid form of NaCDC is prepared according to the methods described herein (e.g., according to slurry, ultrasonic slurry, slow evaporation, solvent drip milling, vapor diffusion onto a solid, antisolvent vapor diffusion into a solution, rapid cooling, forward antisolvent addition, or reverse antisolvent addition methods, as described in the Examples herein).

[0235] In some embodiments, the suitable solvent is methyl isobutyl ketone (MIBK), n-butanol, water or a mixture thereof. In some embodiments, the suitable solvent is selected from acetone, acetonitrile, n-butyl acetate, diisopropyl ether, ethanol, 2-ethoxyethanol, ethyl acetate, ether, n-heptane, isopropyl acetate, methanol, methyl ethyl ketone, methyl tert-butyl ether, 2-propanol, 2,2,2-trifluoroethanol, toluene, water or a mixture thereof.

[0236] In some embodiments, the method for preparing the solid form of NaCDC includes the step of heating the mixture comprising NaCDC to a suitable temperature. In some embodiments, the method for preparing the solid form of NaCDC includes the step of stirring the mixture comprising NaCDC at ambient temperature. In some embodiments, the method for preparing the solid form of NaCDC includes the step of cooling the mixture comprising NaCDC to a suitable temperature.

[0237] In some embodiments, the solid form of NaCDC is precipitated from a mixture (e.g., a solution, a suspension, or a slurry). In some embodiments, the solid form of NaCDC is crystallized from a solution. In some embodiments, the solid form of NaCDC is crystallized from a solution after solution seeding (e.g., adding a crystal of NaCDC to a solution). In some embodiments, after cooling, adding an antisolvent and / or removing part or all of the solvent by a method such as evaporation, distillation, filtration, reverse osmosis, absorption, or reaction, the solid form of NaCDC is precipitated or crystallized from a mixture.

[0238] In some embodiments, the method for preparing the solid form of NaCDC includes the step of separating the solid form.It should be understood that the solid form of NaCDC can be separated by any suitable means.In some embodiments, the solid form of NaCDC is separated from the supernatant by filtering.In some embodiments, the solid form of NaCDC is separated from the supernatant by decantation.In some embodiments, the solid form of NaCDC is separated from the supernatant by centrifugation.

[0239] In some embodiments, the isolated solid form of NaCDC is dried (eg, in air or under reduced pressure, optionally at elevated temperature).

[0240] In some embodiments, the solid form of NaCDC is prepared by converting a solid form of NaCDC into another solid form of NaCDC. For example, in some embodiments, as described in the Examples herein, the solid form of NaCDC (e.g., any of Forms S1, S2, S3, S4, S5, S6, S7, S9-a, S9-b, S10, S11, S12, S13, S14, and / or S15) is prepared by converting NaCDC Form B.

[0241] In some embodiments, the solid form of NaCDC is prepared by a method comprising the steps of combining CDCA in a suitable solvent (e.g., methyl isobutyl ketone). In some embodiments, the combination step comprises stirring the mixture at a suitable temperature (e.g., ambient temperature). In some embodiments, the method further comprises adding a suitable base (e.g., sodium hydroxide, for example, as an aqueous solution). In some embodiments, the method further comprises heating the mixture to reflux (e.g., azeotropic reflux). In some embodiments, the method further comprises distilling off a portion of the solvent, for example, until a vapor temperature of about 117°C is observed. In some embodiments, the method further comprises cooling the mixture to a suitable temperature (e.g., ambient temperature). In some embodiments, the method further comprises shaking or stirring the mixture (e.g., at ambient temperature). In some embodiments, the method further comprises separating the solid form of NaCDC (e.g., Form A) by a suitable method (such as filtration). In some embodiments, the method comprises the following steps: providing a mixture of chenodeoxycholic acid in methyl isobutyl ketone; adding an aqueous sodium hydroxide solution to the mixture; heating the mixture; and removing the solvent to provide NaCDC Form A.

[0242] In some embodiments, the present disclosure provides a method for preparing a solid form of NaCDC, the method comprising the step of combining CDCA in a suitable solvent (e.g., methyl isobutyl ketone). In some embodiments, the combination step comprises stirring the mixture at a suitable temperature (e.g., ambient temperature). In some embodiments, the method further comprises adding a suitable base (e.g., sodium hydroxide, for example, as an aqueous solution). In some embodiments, the method further comprises heating the mixture to reflux (e.g., azeotropic reflux). In some embodiments, the method further comprises distilling off a portion of the solvent, for example, until a vapor temperature of about 117°C is observed. In some embodiments, the method further comprises cooling the mixture to a suitable temperature (e.g., ambient temperature). In some embodiments, the method further comprises shaking or stirring the mixture (e.g., at ambient temperature). In some embodiments, the method further comprises separating the solid form of NaCDC (e.g., Form A) by a suitable method (such as filtration). In some embodiments, the method comprises the following steps: providing a mixture of chenodeoxycholic acid in methyl isobutyl ketone; adding an aqueous sodium hydroxide solution to the mixture; heating the mixture; and removing the solvent to provide NaCDC Form A.

[0243] In some embodiments, the solid form of NaCDC is prepared by a method comprising combining CDCA in a suitable solvent (e.g., n-butanol). In some embodiments, the combination step includes stirring the mixture at a suitable temperature (e.g., ambient temperature). In some embodiments, the method further includes adding a suitable base (e.g., sodium hydroxide, for example, as an aqueous solution). In some embodiments, the method further includes heating the mixture to reflux (e.g., azeotropic reflux). In some embodiments, the method further includes distilling off a portion of the solvent, for example, until a vapor temperature of about 117°C is observed. In some embodiments, the method further includes cooling the mixture to a suitable temperature (e.g., ambient temperature). In some embodiments, the method further includes shaking or stirring the mixture (e.g., at ambient temperature). In some embodiments, the method further includes separating the solid form of NaCDC (e.g., Form B) by a suitable method (such as filtration). In some embodiments, the method includes the following steps: providing a mixture of chenodeoxycholic acid in n-butanol; adding an aqueous sodium hydroxide solution to the mixture; heating the mixture; and removing the solvent to provide NaCDC Form B.

[0244] In some embodiments, the present disclosure provides a method for preparing a solid form of NaCDC, the method comprising the step of combining CDCA in a suitable solvent (e.g., n-butanol). In some embodiments, the combination step comprises stirring the mixture at a suitable temperature (e.g., ambient temperature). In some embodiments, the method further comprises adding a suitable base (e.g., sodium hydroxide, for example, as an aqueous solution). In some embodiments, the method further comprises heating the mixture to reflux (e.g., azeotropic reflux). In some embodiments, the method further comprises distilling off a portion of the solvent, for example, until a vapor temperature of about 117°C is observed. In some embodiments, the method further comprises cooling the mixture to a suitable temperature (e.g., ambient temperature). In some embodiments, the method further comprises shaking or stirring the mixture (e.g., at ambient temperature). In some embodiments, the method further comprises separating the solid form of NaCDC (e.g., Form B) by a suitable method (such as filtration). In some embodiments, the method comprises the following steps: providing a mixture of chenodeoxycholic acid in n-butanol; adding an aqueous sodium hydroxide solution to the mixture; heating the mixture; and removing the solvent to provide NaCDC Form B.

[0245] Composition

[0246] In some embodiments, the disclosure also provides a composition comprising one or more solid forms of CDCA and / or NaCDC. In some embodiments, the composition provided comprises amorphous CDCA, crystalline CDCA, amorphous NaCDC, crystalline NaCDC (e.g., form A or form B, or any other form provided herein), or a mixture thereof. In some embodiments, the composition provided comprises NaCDC form A. In some embodiments, the composition provided comprises NaCDC form B.

[0247] In some embodiments, the composition provided comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) is substantially free of impurities. As used herein, the term "substantially free of impurities" means that the composition does not contain a significant amount of foreign matter. Such foreign matter may include starting materials, residual solvents or any other impurities, which may be produced by the preparation and / or separation of the crystalline solid form. In some embodiments, the composition comprises at least about 90% by weight of the crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein). In some embodiments, the composition comprises at least about 95% by weight of the crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein). In some embodiments, the composition comprises at least about 99% by weight of the crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein).

[0248] In some embodiments, the composition provided comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) is substantially pure (e.g., based on the total weight of the composition, comprising at least about 95 wt%, 97 wt%, 97.5 wt%, 98 wt%, 98.5 wt%, 99 wt%, 99.5 wt%, or 99.8 wt% of the crystalline solid form). In some embodiments, the composition comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) comprises no more than about 5.0% total organic impurities. In some embodiments, the composition comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) comprises no more than about 3.0% total organic impurities. In some embodiments, the composition comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) comprises no more than about 1.5% total organic impurities. In some embodiments, the composition comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) comprises no more than about 1.0% total organic impurities. In some embodiments, the composition comprising a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) comprises no more than about 0.5% total organic impurities. In some embodiments, the percentage of total organic impurities is measured by HPLC.

[0249] In some embodiments, the composition comprises a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein) and an amorphous solid form (e.g., amorphous CDCA and / or amorphous NaCDC). In some embodiments, the composition comprising a crystalline solid form is substantially free of amorphous solid forms. As used herein, the term "substantially free of amorphous solid forms" means that the composition does not contain a significant amount of amorphous solid forms. In some embodiments, the composition comprises at least about 90% by weight of a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein). In some embodiments, the composition comprises at least about 95% by weight of a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein). In some embodiments, the composition comprises at least about 99% by weight of a crystalline solid form (e.g., NaCDC Form A or NaCDC Form B, or any other form provided herein). In some embodiments, the composition comprises no more than about 10% by weight of an amorphous solid form (e.g., amorphous CDCA and / or amorphous NaCDC). In some embodiments, the composition comprises no more than about 5% by weight of an amorphous solid form (e.g., amorphous CDCA and / or amorphous NaCDC). In some embodiments, the composition comprises no more than about 1% by weight of an amorphous solid form (e.g., amorphous CDCA and / or amorphous NaCDC).

[0250] In some embodiments, the composition comprises a free acid form (e.g., CDCA) and a salt form (e.g., NaCDC). In some such embodiments, the free acid form is crystalline, amorphous, or a mixture thereof; in some such embodiments, the salt form is crystalline, amorphous, or a mixture thereof.

[0251] In some embodiments, the composition comprises a mixture of crystalline solid forms (eg, a mixture of one or more crystalline forms of CDCA and / or NaCDC).

[0252] Pharmaceutical composition

[0253] In some embodiments, the present disclosure provides a pharmaceutical composition comprising NaCDC (e.g., in a crystalline form, such as Form A or Form B, or any other form provided herein) and a pharmaceutically acceptable carrier. In some embodiments, the present disclosure provides a pharmaceutical composition comprising a solid form of NaCDC (e.g., a solid form described herein) and a pharmaceutically acceptable carrier. In some embodiments, a pharmaceutical composition is provided comprising NaCDC (i.e., in a suitable form, such as a crystalline form described herein) and one or more fillers, disintegrants, lubricants, glidants, anti-adherents and / or antistatic agents, etc.

[0254] The pharmaceutical compositions of the present disclosure can be administered orally, parenterally, by inhalation of an aerosol, topically, rectally, nasally, buccally, vaginally, intraperitoneally, intracisternal, or via an implanted reservoir. In some embodiments, provided pharmaceutical compositions are administered orally, intraperitoneally, or intravenously. In some embodiments, provided pharmaceutical compositions are administered orally.

[0255] In some embodiments, the pharmaceutical composition provided is an oral dosage form (e.g., a capsule or tablet). In some embodiments, the pharmaceutical composition provided is a tablet. In some embodiments, the pharmaceutical composition provided is a bilayer tablet (e.g., as described herein). In some embodiments, the pharmaceutical composition provided is a capsule.

[0256] In some embodiments, provided pharmaceutical compositions are solid pharmaceutical compositions (eg, solid dosage forms such as capsules or tablets).

[0257] In some embodiments, the solid form of NaCDC provided can be used to prepare a previously reported pharmaceutical composition comprising CDCA or its salt. For example, PCT Publication No. WO 2021 / 030474 (the entire contents of which are incorporated herein by reference) describes certain products and compositions for delivering therapeutic agents (including CDCA or its salt) to the colon of a subject. Therefore, in some embodiments, the solid form provided can be used to prepare the products and compositions described therein.

[0258] In some embodiments, the pharmaceutical composition provided is a product (e.g., a tablet) comprising: a first part comprising a secretion inducer (e.g., CDCA or a salt thereof, e.g., NaCDC, e.g., in a solid form as described herein); a second part adjacent to the first part, comprising a therapeutic agent (e.g., CDCA or a salt thereof, e.g., NaCDC, e.g., in a solid form as described herein); and a degradable coating associated with the product. In some embodiments, the secretion inducer is configured to increase the water content in the colon of the subject. In some embodiments, the local concentration of the secretion inducer is at least 3 mM. In some embodiments, the secretion inducer is configured to increase the amount of intestinal fluid present in the intestine of the subject. In some embodiments, the secretion inducer is configured to completely dissolve within one-fifth of the distance between the ileocecal valve and the hepatic flexure. In some embodiments, the secretion inducer is configured to increase the motility of the gastrointestinal tract of the subject. In some embodiments, the product comprises a secretion inducer in an amount greater than or equal to 5 mg and less than or equal to 5 g. In some embodiments, the product comprises a secretion inducer, the weight % of which relative to the total weight of the product is greater than or equal to 10 weight % and less than or equal to 95 weight %. In some embodiments, the product is configured to release the therapeutic agent in the colon of the subject. In some embodiments, the product comprises a therapeutic agent in an amount greater than or equal to 10 mg and less than or equal to 10 g. In some embodiments, the product comprises a therapeutic agent, the weight % relative to the total weight of the product being greater than or equal to 10 weight % and less than or equal to 95 weight %. In some embodiments, the mass ratio of the secretion inducer to the therapeutic agent is 10:90 to 90:10. In some embodiments, the mass ratio of the first part to the second part is 1:1 to 1:99. In some embodiments, the degradable coating comprises Eudragit S100, Phloral, HPMC or Duocoat. In some embodiments, the product further comprises hydroxypropyl methylcellulose (HPMC). In some embodiments, the product further comprises magnesium stearate.

[0259] In some embodiments, the pharmaceutical composition provided is a product (e.g., tablet) comprising: a first component configured to increase the amount of intestinal fluid present in the subject's intestinal tract; and a second component associated with the first component, which is configured to release the therapeutic agent in the subject's intestinal tract. In some embodiments, the first component comprises CDCA or a salt thereof (e.g., NaCDC, e.g., in a solid form as described herein). In some embodiments, the second component comprises CDCA or a salt thereof (e.g., NaCDC, e.g., in a solid form as described herein). In some embodiments, the product is configured to release the therapeutic agent in a portion of the subject's intestinal tract (e.g., colon).

[0260] In some embodiments, the pharmaceutical composition provided is a product (e.g., a tablet) comprising: a first portion comprising bile acid or a salt thereof (e.g., CDCA or a salt thereof, e.g., NaCDC, e.g., in a solid form as described herein), wherein the first portion is configured for immediate release in the colon of a subject; a second portion adjacent to the first portion, the second portion comprising bile acid or a salt thereof (e.g., CDCA or a salt thereof, e.g., NaCDC, e.g., in a solid form as described herein), and wherein the second portion is configured for extended release in the colon of a subject; and a degradable or erodible coating associated with the product. In some embodiments, the product is a pill, tablet, or capsule. In some embodiments, the first portion is configured to completely dissolve within one-fifth of the distance between the ileocecal valve and the hepatic flexure of the subject. In some embodiments, the first portion is configured to produce a local colon concentration of bile acid of at least 3 mM. In some embodiments, the second portion further comprises hydroxypropyl methylcellulose (HPMC). In some embodiments, the coating is configured to release bile acid or a salt thereof from the first portion in the colon of the subject. In some embodiments, the coating is or comprises Eudragit S100.

[0261] In some embodiments, the ratio of the first part or component to the second part or component (e.g., weight ratio or height ratio) is greater than or equal to 1:1, greater than or equal to 1:2, greater than or equal to 1:3, greater than or equal to 1:4, greater than or equal to 1:5, greater than or equal to 1:10, greater than or equal to 1:20, greater than or equal to 1:30, greater than or equal to 1:40, greater than or equal to 1:50, greater than or equal to 1:60, greater than or equal to 1:70, greater than or equal to 1:75, greater than or equal to 1:80, greater than or equal to 1:85, greater than or equal to 1:90, greater than or equal to 1:95, greater than or equal to 1:96, greater than or equal to 1:97, greater than or equal to 1:98, or greater than or equal to 1:99. In some embodiments, the ratio of the first part or component to the second part or component (e.g., weight ratio or height ratio) is less than or equal to 1:1, less than or equal to 1:2, less than or equal to 1:3, less than or equal to 1:4, less than or equal to 1:5, less than or equal to 1:10, less than or equal to 1:20, less than or equal to 1:30, less than or equal to 1:40, less than or equal to 1:50, less than or equal to 1:60, less than or equal to 1:70, less than or equal to 1:75, less than or equal to 1:80, less than or equal to 1:85, less than or equal to 1:90, less than or equal to 1:95, less than or equal to 1:96, less than or equal to 1:97, less than or equal to 1:98, or less than or equal to 1:99. Combinations of the above-mentioned ranges are also possible (e.g., less than or equal to 1:1 and greater than or equal to 1:99).

[0262] In some embodiments, the ratio of the second part or component to the first part or component (e.g., weight ratio or height ratio) is greater than or equal to 1:1, greater than or equal to 1:2, greater than or equal to 1:3, greater than or equal to 1:4, greater than or equal to 1:5, greater than or equal to 1:10, greater than or equal to 1:20, greater than or equal to 1:30, greater than or equal to 1:40, greater than or equal to 1:50, greater than or equal to 1:60, greater than or equal to 1:70, greater than or equal to 1:75, greater than or equal to 1:80, greater than or equal to 1:85, greater than or equal to 1:90, greater than or equal to 1:95, greater than or equal to 1:96, greater than or equal to 1:97, greater than or equal to 1:98, or greater than or equal to 1:99. In some embodiments, the ratio of the second part or component to the first part or component (e.g., weight ratio or height ratio) is less than or equal to 1:1, less than or equal to 1:2, less than or equal to 1:3, less than or equal to 1:4, less than or equal to 1:5, less than or equal to 1:10, less than or equal to 1:20, less than or equal to 1:30, less than or equal to 1:40, less than or equal to 1:50, less than or equal to 1:60, less than or equal to 1:70, less than or equal to 1:75, less than or equal to 1:80, less than or equal to 1:85, less than or equal to 1:90, less than or equal to 1:95, less than or equal to 1:96, less than or equal to 1:97, less than or equal to 1:98, or less than or equal to 1:99. Combinations of the above-mentioned ranges are also possible (e.g., less than or equal to 1:1 and greater than or equal to 1:99).

[0263] In some embodiments, the pharmaceutical composition provided comprises a secretion inducer. In some embodiments, a secretion inducer is a chemical substance that stimulates the increase of intestinal fluid release along the gastrointestinal tract (e.g., relative to the basal release of intestinal fluid and / or in response to the basal release of intestinal fluid of foreign matter (such as food) present in the gastrointestinal tract). In this way, the increased amount of intestinal fluid enhances the solubility and / or absorption of the therapeutic agent. In some embodiments, the secretion inducer is a bile acid (e.g., CDCA) or a salt thereof. In some embodiments, the secretion inducer is NaCDC. In some embodiments, the secretion inducer comprises bisacodyl, senna, sennoside, linaclotide, plecanatide, lubiprostone, 30 methylnaltrexone, naloxegol, polyethylene glycol, lactulose or prucalopride. In some embodiments, the secretion inducer can be a salt, such as magnesium citrate, magnesium hydroxide or bile salts, as non-limiting examples. Other secretion inducers are also possible, as any chemical that stimulates the release of intestinal fluid along the gastrointestinal tract can act as a secretion inducer.

[0264] In some embodiments, the weight % of the secretion inducer relative to the total weight of the product or composition (e.g., tablets, capsules, etc.) is greater than or equal to 10 weight %, greater than or equal to 15 weight %, greater than or equal to 20 weight %, greater than or equal to 25 weight %, greater than or equal to 30 weight %, greater than or equal to 40 weight %, greater than or equal to 50 weight %, greater than or equal to 60 weight %, greater than or equal to 70 weight %, greater than or equal to 75 weight %, greater than or equal to 80 weight %, greater than or equal to 90 weight % or greater than or equal to 95 weight %. In some embodiments, the weight % of the secretion inducing agent relative to the total weight of the product or composition (e.g., tablets, capsules, etc.) is less than or equal to 95 weight %, less than or equal to 90 weight %, less than or equal to 80 weight %, less than or equal to 75 weight %, less than or equal to 70 weight %, less than or equal to 60 weight %, less than or equal to 50 weight %, less than or equal to 40 weight %, less than or equal to 30 weight %, less than or equal to 25 weight %, less than or equal to 20 weight %, less than or equal to 15 weight % or less than or equal to 10 weight %. Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 10 weight % and less than or equal to 50 weight %). Other ranges are possible.

[0265] In some embodiments, the amount (e.g., mass) of the secretion inducer present in an article or composition (e.g., tablet, capsule, etc.) is greater than or equal to 5 mg, greater than or equal to 10 mg, greater than or equal to 20 mg, greater than or equal to 20 mg, greater than or equal to 30 mg, greater than or equal to 50 mg, greater than or equal to 60 mg, greater than or equal to 70 mg, greater than or equal to 75 mg, greater than or equal to 80 mg, greater than or equal to 90 mg, greater than or equal to 95 mg, greater than or equal to 100 mg, greater than or equal to 250 mg, greater than or equal to 500 mg, greater than or equal to 750 mg, greater than or equal to 1 g, greater than or equal to 2 g, greater than or equal to 3 g, greater than or equal to 4 g, or greater than or equal to 5 g. In some embodiments, the amount of secretion inducer present in the article or composition (e.g., tablet, capsule, etc.) is less than or equal to 5 g, less than or equal to 4 g, less than or equal to 3 g, less than or equal to 2 g, less than or equal to 1 g, less than or equal to 750 mg, less than or equal to 500 mg, less than or equal to 250 mg, less than or equal to 100 mg, less than or equal to 95 mg, less than or equal to 30 90 mg, less than or equal to 80 mg, less than or equal to 75 mg, less than or equal to 70 mg, less than or equal to 60 mg, less than or equal to 50 mg, less than or equal to 40 mg, less than or equal to 30 mg, less than or equal to 25 mg, less than or equal to 20 mg, less than or equal to 10 mg, or less than or equal to 5 mg. Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 5 mg and less than or equal to 5 g). Other ranges are possible.

[0266] In some embodiments, the pharmaceutical composition provided comprises a therapeutic agent. In some embodiments, the therapeutic agent can be a therapeutic agent, a diagnostic agent and / or an enhancer, such as one or a combination of a drug, a nutrient, a microorganism, an in vivo sensor and a tracer. In some embodiments, the therapeutic agent is a nutrient, a preventive or a diagnostic agent. The therapeutic agent may include but is not limited to any synthetic or naturally occurring bioactive compound or substance composition, which, when applied to a subject (human or non-human animal), induces desired pharmacology, immunogenicity and / or physiological effects by local and / or systemic effects (such as increasing the amount of intestinal fluid present in the subject's colon). For example, in some embodiments, the therapeutic agent includes chemicals that are traditionally regarded as drugs, vaccines and biopharmaceuticals. Lists of examples of known therapeutic agents can be found, for example, in the United States Pharmacopeia (USP); The Pharmacological Basis of Therapeutics, 13th Edition, McGraw Hill, 2017 by Goodman and Gilman; Katzung, B. and Vanderah, TW (eds.) Basic and Clinical Pharmacology, McGraw-Hill; 15th Edition (December 5, 2020); Prescriber's Digital Reference (pdr.net); The Merck Manual 20th Edition (2018), Porter, RE (ed.), Wiley; or in the case of animals, The Merck Veterinary Manual, 11th Edition, Kahn, CA (ed.), Merck Manuals, 2016; and in "Approved Drug Products with Therapeutic Equivalence and Evaluations," (the "Orange Book") published by the United States Food and Drug Administration (FDA).

[0267] In some embodiments, the therapeutic agent is bile acid (e.g., CDCA) or a salt thereof. In some embodiments, the therapeutic agent is NaCDC. The non-limiting examples of bile acid include chenodeoxycholic acid, ursodeoxycholic acid, deoxycholic acid, taurocholic acid, glycocholic acid, cholic acid, taurochenodeoxycholic acid, glycochenodeoxycholic acid, deoxycholic acid and lithocholic acid. Therefore, in some embodiments, the therapeutic agent is selected from the group consisting of: chenodeoxycholic acid, ursodeoxycholic acid, deoxycholic acid, taurocholic acid, glycocholic acid, cholic acid, taurochenodeoxycholic acid, glycochenodeoxycholic acid, deoxycholic acid and lithocholic acid or a salt thereof.

[0268] In some embodiments, the weight % of the therapeutic agent relative to the total weight of the article or composition (e.g., tablet, capsule, etc.) is greater than or equal to 10 weight %, greater than or equal to 15 weight %, greater than or equal to 20 weight %, greater than or equal to 25 weight %, greater than or equal to 30 weight %, greater than or equal to 40 weight %, greater than or equal to 50 weight %, greater than or equal to 60 weight %, greater than or equal to 70 weight %, greater than or equal to 75 weight %, greater than or equal to 80 weight %, greater than or equal to 90 weight % or greater than or equal to 95 weight %. In some embodiments, the weight % of the therapeutic agent relative to the total weight of the article or composition (e.g., tablets, capsules, etc.) is less than or equal to 95 weight %, less than or equal to 90 weight %, less than or equal to 80 weight %, less than or equal to 75 weight %, less than or equal to 70 weight %, less than or equal to 60 weight %, less than or equal to 50 weight %, less than or equal to 40 weight %, less than or equal to 30 weight %, less than or equal to 25 weight %, less than or equal to 20 weight %, less than or equal to 15 weight % or less than or equal to 10 weight %. Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 10 weight % and less than or equal to 50 weight %). Other ranges are possible.

[0269] In some embodiments, the amount (e.g., mass) of therapeutic agent present in an article or composition (e.g., tablet, capsule, etc.) is greater than or equal to 10 mg, greater than or equal to 20 mg, greater than or equal to 25 mg, greater than or equal to 60 mg, greater than or equal to 70 mg, greater than or equal to 75 mg, greater than or equal to 80 mg, greater than or equal to 90 mg, greater than or equal to 95 mg, greater than or equal to 100 mg, greater than or equal to 250 mg, greater than or equal to 300 mg, greater than or equal to 400 mg, greater than or equal to 500 mg, greater than or equal to 750 mg, greater than or equal to 1 g, greater than or equal to 2 g, greater than or equal to 3 g, greater than or equal to 4 g, greater than or equal to 5 g, greater than or equal to 6 g, greater than or equal to 7 g, greater than or equal to 8 g, greater than or equal to 9 g, or greater than or equal to 10 g. In some embodiments, the amount (e.g., mass) of the therapeutic agent present in the article or composition (e.g., tablet, capsule, etc.) is less than or equal to 10 mg, less than or equal to 20 mg, less than or equal to 25 mg, less than or equal to 60 mg, less than or equal to 70 mg, less than or equal to 75 mg, less than or equal to 80 mg, less than or equal to 90 mg, less than or equal to 95 mg, less than or equal to 100 mg, less than or equal to 250 mg, less than or equal to 300 mg, less than or equal to 400 mg, less than or equal to 500 mg, less than or equal to 750 mg, less than or equal to 1 g, less than or equal to 2 g, less than or equal to 3 g, less than or equal to 4 g, less than or equal to 5 g, less than or equal to 6 g, less than or equal to 7 g, less than or equal to 8 g, less than or equal to 9 g, or less than or equal to 10 g. Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 10 mg and less than or equal to 10 g). Other ranges are possible.

[0270] In some embodiments, the mass ratio of secretion inducer to therapeutic agent is greater than or equal to 10:90, greater than or equal to 20:80, greater than or equal to 30:70, greater than or equal to 40:60, greater than or equal to 50:50, greater than or equal to 60:40, greater than or equal to 70:30, greater than or equal to 80:20, or greater than or equal to 90:10. In some embodiments, the mass ratio of secretion inducer to therapeutic agent is less than or equal to 90:10, less than or equal to 80:20, less than 10 or equal to 70:30, less than or equal to 60:40, less than or equal to 50:50, less than or equal to 40:60, less than or equal to 30:70, less than or equal to 20:80, or less than or equal to 10:90. Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 10:90 and less than or equal to 30:70). Other ranges are possible.

[0271] In some embodiments, the pharmaceutical composition provided comprises a coating. In some embodiments, the coating is degradable and / or erodible (e.g., eroded by gastrointestinal fluid under physiological conditions). In some embodiments, the coating is or comprises Eudragit S100. Any suitable coating can be used, which is configured to release the secretion inducer to the desired part of the gastrointestinal tract (such as in the distal part of the ileum or the distal part of the colon, as a non-limiting example). Non-limiting examples of suitable degradable coatings include Eudragit S, Phloral, CODES and Duocoat. In some embodiments, the coating is or comprises, for example, hydroxypropyl methylcellulose (HPMC). Other coatings are also possible.

[0272] In some embodiments, provided pharmaceutical compositions include one or more additional components (e.g., excipients). In some embodiments, additional components can contribute to the stability of the composition, the solubility of the composition, and / or the ability of the composition to deliver the therapeutic agent to a desired portion of the gastrointestinal tract. In some embodiments, the additional component is magnesium stearate. In some embodiments, the additional component is hydroxypropyl methylcellulose. In some embodiments, the additional component is 200Pharma. In some embodiments, the additional components are selected from microcrystalline cellulose (e.g., Avicel PH102), cross-linked sodium carboxymethylcellulose, copolyvidone, magnesium stearate, calcium hydrogen phosphate dihydrate, sodium starch glycolate, sodium stearyl fumarate, poly (ethylene oxide) (e.g., PolyOX WSR1105) and hydroxypropyl methylcellulose (e.g., HPMC K4M). In some embodiments, the additional components can form a matrix around or inside the composition. In some embodiments, the additional components can control the release of one or more other components of the composition (e.g., secretion inducer or therapeutic agent). Non-limiting examples of suitable matrix forming agents and / or release control agents include methylcellulose, hydroxypropyl cellulose, hydroxypropyl methylcellulose, alginate, gums of plant origin, chitosan, gelatin, pectin, carrageenan, polyacrylates, polyethylene oxide and starch. Examples of hydrophobic matrix forming agents and / or release controlling agents include waxes, fatty acids, fatty alcohols and esters, glycerides, polyesteramides, ethylcellulose, polyethylene, polypropylene, polythiourethane, polyvinyl butyral, polylactic acid, poly(lactide-co-glycolide), cellulose acetate, and cellulose acetate butyrate. Other additional components that may aid in the delivery of secretion inducing agents or therapeutic agents are also possible.

[0273] In some embodiments, provided pharmaceutical compositions may include a hydrophilic agent. Non-limiting examples of suitable hydrophilic agents include cyclodextrins, surfactants, solid buffers (e.g., sodium citrate / citric acid). As the present disclosure is not limited thereto, other examples of hydrophilic agents are also possible.

[0274] In some embodiments, the pharmaceutical composition provided is configured so that when administered to a subject, the secretion inducer is present at a local concentration of at least 3mM along the gastrointestinal tract. In some embodiments, the local concentration is at least 5mM. In some embodiments, a local concentration of at least 3mM, at least 5mM, at least 10mM, at least 15mM, at least 20mM, at least 30mM or at least 50mM is produced. In some embodiments, a local concentration of less than or equal to 100mM, less than or equal to 50mM, less than or equal to 30mM, less than or equal to 20mM, less than or equal to 15mM, less than or equal to 10mM or less than or equal to 5mM is produced. As described herein, "local concentration" refers to the amount of a substance per unit volume at a location near the product. For example, the concentration of the secretion inducer along the entire gastrointestinal tract may be substantially less than 3mM, but the concentration of the secretion inducer near the composition or product provided may be equal to or greater than 3mM.

[0275] In some embodiments, provided pharmaceutical compositions have a maximum cross-sectional dimension (e.g., diameter) of at least 10 mm, at least 12 mm, at least 14 mm, at least 15 mm, at least 18 mm, at least 19 mm, at least 21 mm, at least 23 mm, or at least 26. In some embodiments, provided pharmaceutical compositions have a maximum cross-sectional dimension of at most 27 mm, at most 24 mm, at most 22 mm, at most 20 mm, at most 18 mm, at most 16 mm, at most 15 mm, or at most 10 mm.

[0276] In some embodiments, a pharmaceutical composition is provided that is a bilayer tablet coated with Eudragit S100, the bilayer tablet comprising: a first layer comprising 81% NaCDC, 17% hydroxypropylmethylcellulose (HPMC) (MW: 120,000) and 2% magnesium stearate; and a second layer comprising 98% NaCDC and 2% magnesium stearate. In some such embodiments, the bilayer tablet comprises 400 mg NaCDC in the first layer. In some such embodiments, the bilayer tablet comprises 98 mg NaCDC in the second layer.

[0277] In some embodiments, a pharmaceutical composition is provided that is a bilayer tablet coated with Eudragit S100, the bilayer tablet comprising: a first layer comprising 87.5% NaCDC, 10% HPMC (MW: 120,000), 2% magnesium stearate, and 0.5% Aerosil 200; and a second layer comprising 97.5% NaCDC, 2% magnesium stearate, and 0.5% Aerosil 200. In some such embodiments, the bilayer tablet comprises 400 mg NaCDC in the first layer. In some such embodiments, the bilayer tablet comprises 100 mg NaCDC in the second layer.

[0278] In some embodiments, provided pharmaceutical compositions are prepared by: (i) providing NaCDC in any suitable form, such as a crystalline form described herein; and (ii) formulating the NaCDC with a suitable excipient to provide the pharmaceutical composition.

[0279] use

[0280] The present disclosure provides the purposes of solid forms and compositions as described herein. In some embodiments, the solid forms provided and compositions thereof can be used for medicine (e.g., as therapy). In some embodiments, the solid forms provided as described herein and compositions can be used for research, e.g., as analytical tools and / or controls.

[0281] In some embodiments, the present disclosure provides a method for applying a solid form and a composition thereof to a subject in need thereof. In some embodiments, the present disclosure provides a method for applying a solid form and a composition thereof to a subject suffering from a gastrointestinal disorder (e.g., constipation, e.g., IBS-C). In some embodiments, the present disclosure provides a method for applying a solid form and a composition thereof to a subject suffering from a systemic disorder (e.g., a disorder in which a therapy (e.g., a solid form or a composition thereof) is administered to the gastrointestinal tract to effectively treat a systemic disorder). In some embodiments, the present disclosure provides a method for applying a solid form and a composition thereof to a subject requiring a colonoscopy (e.g., for diagnosing colorectal lesions). In some embodiments, the present disclosure provides a method for applying a solid form and a composition thereof to a subject suffering from constipation, ulcerative colitis, Crohn's disease (Crohn's disease), diabetes, metabolic disorders, obesity, travelers' diarrhea, hepatic encephalopathy, or a disease associated with biome regulation. In some embodiments, such methods include orally administering a solid form or a composition thereof to a subject.

[0282] It should be understood that as used herein, "subject" refers to an organism, typically a mammal (e.g., a human, a non-human mammal, a non-human primate, a primate, a mouse, a rat, a hamster, a gerbil, a cat, a dog, etc.). In some embodiments, the subject is a human.

[0283] In some embodiments, the disclosure provides a method for delivering a therapeutic agent (e.g., bile acid, e.g., CDCA or its salt) to the intestinal tract (e.g., colon) of a subject in need. In some embodiments, such methods include administering a solid form or composition, e.g., comprising one or more solid forms provided herein, as described herein, or a composition prepared therefrom. In some embodiments, such methods include administering a solid form or its composition provided orally to a subject.

[0284] In some embodiments, the disclosure provides a method for treating a disease, disorder or illness, which includes applying a solid form or its composition provided to a subject in need. As used herein, "treat", "treatment" or "treating" refers to partially or completely alleviating, improving, alleviating, suppressing one or more symptoms, characteristics and / or causes of a specific disease, disorder and / or illness, delaying its onset, reducing its severity and / or reducing its incidence. The application of the therapy. In some embodiments, such treatments may be directed to subjects who do not show signs of related diseases, disorders and / or illnesses and / or to subjects who only show early signs of diseases, disorders and / or illnesses. Alternatively or additionally, such treatments may be directed to subjects who show one or more determined signs of related diseases, disorders and / or illnesses. In some embodiments, treatment may be directed to subjects who have been diagnosed with related diseases, disorders and / or illnesses. In some embodiments, treatment may be directed to subjects who are known to have one or more susceptibility factors statistically associated with an increased risk of the development of related diseases, disorders and / or illnesses. Thus, in some embodiments, treatment may be prophylactic; in some embodiments, treatment may be therapeutic.

[0285] In some embodiments, the present disclosure provides a method for treating a gastrointestinal disorder (e.g., constipation, e.g., IBS-C), comprising administering a solid form or a composition thereof to a subject in need thereof. In some embodiments, the method provided achieves certain desired results, such as, for example, improved efficacy and / or reduced incidence of abdominal pain and / or cramping (e.g., compared to another preparation of CDCA or its salt). In some embodiments, such methods include orally administering a solid form or a composition thereof to a subject.

[0286] In some embodiments, the present disclosure provides methods for treating systemic disorders (e.g., disorders in which administration of a therapy (e.g., a provided solid form or composition thereof) to the gastrointestinal tract is effective for treating the systemic disorder), comprising administering a provided solid form or composition thereof to a subject in need thereof. In some embodiments, the present disclosure provides methods for treating a disease, disorder, or condition selected from the group consisting of constipation, ulcerative colitis, Crohn's disease, diabetes, metabolic disorders, obesity, traveler's diarrhea, hepatic encephalopathy, and diseases associated with biome regulation, comprising administering a provided solid form or composition thereof to a subject in need thereof. In some embodiments, such methods comprise orally administering a provided solid form or composition thereof to a subject.

[0287] In some embodiments, the present disclosure provides a method for diagnosing colorectal lesions, comprising administering a provided solid form or a composition thereof to a subject in need thereof. In some such embodiments, the subject has, is, or will undergo a colonoscopy. In some embodiments, such methods comprise orally administering a provided solid form or a composition thereof to a subject.

[0288] Exemplary embodiments

[0289] The following numbered embodiments (although non-limiting) are exemplary of certain aspects of the present disclosure:

[0290] 1. A crystalline solid form of sodium chenodeoxycholate, wherein the solid form is selected from Form A and Form B.

[0291] 2. The solid form of embodiment 1, wherein the solid form is Form A.

[0292] 3. A solid form as described in embodiment 2, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58 and about 18.34 degrees 2-θ.

[0293] 4. The solid form of embodiment 2, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-θ.

[0294] 5. The solid form of embodiment 2, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the following positions:

[0295] 2θ±0.2[°] 6.07 6.55 8.36 9.92 10.72 11.55 11.93 12.99 13.36 14.64 15.06 15.54 15.93 16.68 16.99 17.31 17.58 18.07 18.34

[0296] 6. The solid form of embodiment 2, wherein the solid form is characterized by one or more of the following:

[0297] (i) Basically similar to Figure 1 The XRPD pattern depicted in;

[0298] (ii) DSC graph showing water loss starting from slightly above ambient temperature and continuing to about 150°C;

[0299] (iii) substantially similar to Figure 2 The DSC diagram depicted in ;

[0300] (iv) a TGA graph showing a weight loss of 4.3% up to 150°C; and

[0301] (v) Basically similar to Figure 3 TGA diagram depicted in .

[0302] 7. The solid form of embodiment 1, wherein the solid form is Form B.

[0303] 8. A solid form as described in embodiment 7, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10 and about 18.63 degrees 2-θ.

[0304] 9. The solid form of embodiment 7, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-theta.

[0305] 10. The solid form of embodiment 7, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the following positions:

[0306]

[0307]

[0308] 11. The solid form of embodiment 7, wherein the solid form is characterized by one or more of the following:

[0309] (i) Basically similar to Figure 5 The XRPD pattern depicted in;

[0310] (ii) DSC graph showing no thermal events from room temperature to about 288°C;

[0311] (iii) substantially similar to Figure 6 The DSC diagram depicted in ;

[0312] (iv) a TGA graph showing a weight loss of <0.1% up to 150°C; and

[0313] (v) Basically similar to Figure 7 TGA diagram depicted in .

[0314] 12. A crystalline solid form of sodium chenodeoxycholate obtainable by the process described herein.

[0315] 13. A crystalline solid form of sodium chenodeoxycholate prepared by a process comprising the steps of: providing a mixture of chenodeoxycholic acid in methyl isobutyl ketone; adding aqueous sodium hydroxide to the mixture; heating the mixture (e.g., to azeotropic reflux); and removing the solvent to provide the crystalline solid form of sodium chenodeoxycholate.

[0316] 14. A crystalline solid form of sodium chenodeoxycholate prepared by a process comprising the steps of: providing a mixture of chenodeoxycholic acid in n-butanol; adding aqueous sodium hydroxide to the mixture; heating the mixture (e.g., to azeotropic reflux); and removing the solvent to provide the crystalline solid form of sodium chenodeoxycholate.

[0317] 15. A crystalline solid form of sodium chenodeoxycholate, wherein the solid form is selected from Form S1, Form S2, Form S3, Form S4, Form S5, Form S6, Form S7, Form S9-a, Form S9-b, Form S10, Form S11, Form S12, Form S13, Form S14 and Form S15.

[0318] 16. The solid form of embodiment 15, wherein the solid form is Form S1.

[0319] 17. The solid form of embodiment 16, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-θ.

[0320] 18. The solid form of embodiment 16, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-theta.

[0321] 19. The solid form of embodiment 16, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S1-A or Table S1-B.

[0322] 20. The solid form of embodiment 16, wherein the solid form is characterized by one or more of the following:

[0323] (i) Basically similar to Fig.19A , Fig.24A and / or Fig.48 The XRPD pattern depicted in;

[0324] (ii) a DSC plot showing thermal events at about 96.0°C, about 142.5°C, and / or about 313.4°C;

[0325] (iii) substantially similar to Fig.19B , Fig. 24B , Fig. 27 and / or Fig.49 The DSC diagram depicted in ;

[0326] (iv) a TGA graph showing a weight loss of about 2.177% up to about 150°C; and

[0327] (v) Basically similar to Fig.19B , Fig. 24B , Fig. 27 and / or Fig.49 TGA diagram depicted in .

[0328] 21. The solid form of embodiment 15, wherein the solid form is Form S2.

[0329] 22. The solid form of embodiment 21, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-theta.

[0330] 23. The solid form of embodiment 21, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-theta.

[0331] 24. The solid form of embodiment 21, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all of the positions listed in Table S2.

[0332] 25. The solid form of embodiment 21, wherein the solid form is characterized by one or more of the following:

[0333] (i) Basically similar to Fig.33 The XRPD pattern depicted in;

[0334] (ii) a DSC graph showing thermal events at about 112.9°C, about 177.8°C, and / or about 334.1°C;

[0335] (iii) substantially similar to Fig.21A , Fig.25 and / or Fig.30 The DSC diagram depicted in ;

[0336] (iv) a TGA graph showing a weight loss of about 3.95% up to about 150°C; and

[0337] (v) Basically similar to Fig.21A , Fig.25 and / or Fig.30 TGA diagram depicted in .

[0338] 26. The solid form of embodiment 15, wherein the solid form is Form S3, Form S6 and / or Form S11.

[0339] 27. The solid form of embodiment 26, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-theta.

[0340] 28. The solid form of embodiment 26, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-theta.

[0341] 29. The solid form of embodiment 26, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all positions listed in Table S3, Table S6, or Table S11.

[0342] 30. The solid form of embodiment 26, wherein the solid form is characterized by one or more of the following:

[0343] (i) Basically similar to Fig. 21B and / or Fig.50A The XRPD pattern depicted in;

[0344] (ii) a DSC plot showing thermal events at about 50.6°C, about 199.8°C, and / or about 331.5°C;

[0345] (iii) substantially similar to Fig.29 and / or Fig.41 The DSC diagram depicted in ;

[0346] (iv) a TGA graph showing a weight loss of about 2.456% up to about 150°C; and

[0347] (v) Basically similar to Fig.29 and / or Fig.41 TGA diagram depicted in .

[0348] 31. The solid form of embodiment 15, wherein the solid form is Form S4.

[0349] 32. The solid form of embodiment 31, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-θ.

[0350] 33. A solid form as described in embodiment 31, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52 and about 16.96 degrees 2-θ.

[0351] 34. A solid form as described in embodiment 31, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all positions listed in Table S4.

[0352] 35. The solid form of embodiment 31, wherein the solid form is characterized by one or more of the following:

[0353] (i) Basically similar to Fig.31A The XRPD pattern depicted in;

[0354] (ii) a DSC graph showing thermal events at about 146.5°C and / or about 333.9°C;

[0355] (iii) substantially similar to Fig. 22 and / or Fig.31B The DSC diagram depicted in ;

[0356] (iv) a TGA graph showing a weight loss of about 14.23% up to about 180°C; and

[0357] (v) Basically similar to Fig. 22 and / or Fig.31B TGA diagram depicted in .

[0358] 36. The solid form of embodiment 15, wherein the solid form is Form S5.

[0359] 37. A solid form as described in embodiment 36, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25 and about 16.68 degrees 2-θ.

[0360] 38. The solid form of embodiment 36, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-theta.

[0361] 39. The solid form of embodiment 36, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all of the positions listed in Table S5.

[0362] 40. The solid form of embodiment 36, wherein the solid form is characterized by one or more of the following:

[0363] (i) Basically similar to Fig.23A The XRPD pattern depicted in;

[0364] (ii) a DSC graph showing thermal events at about 82°C, about 183.9°C, and / or about 331.5°C;

[0365] (iii) substantially similar to Fig. 23B , Fig.28 , Fig.32A , Fig.32B and / or Fig.47 The DSC diagram depicted in ;

[0366] (iv) a TGA graph showing a weight loss of about 4.79% up to about 180°C; and

[0367] (v) Basically similar to Fig. 23B , Fig.28 , Fig.32A , Fig.32B and / or Fig.47 TGA diagram depicted in .

[0368] 41. The solid form of embodiment 15, wherein the solid form is Form S7.

[0369] 42. The solid form of embodiment 41, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-theta.

[0370] 43. The solid form of embodiment 41, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-theta.

[0371] 44. The solid form of embodiment 41, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S7.

[0372] 45. The solid form of embodiment 41, wherein the solid form is characterized by one or more of the following:

[0373] (i) Basically similar to Fig.26A The XRPD pattern depicted in;

[0374] (ii) a DSC graph showing thermal events at about 109.2°C, about 324.5°C, and / or about 335.3°C;

[0375] (iii) substantially similar to Fig.26B The DSC diagram depicted in ;

[0376] (iv) a TGA graph showing a weight loss of about 10.04% up to about 180°C; and

[0377] (v) Basically similar to Fig.26B TGA diagram depicted in .

[0378] 46. ​​The solid form of embodiment 15, wherein the solid form is Form S9-a.

[0379] 47. The solid form of embodiment 46, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-theta.

[0380] 48. The solid form of embodiment 46, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-theta.

[0381] 49. A solid form as described in embodiment 46, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all positions listed in Table S9-a.

[0382] 50. The solid form of embodiment 46, wherein the solid form is characterized by one or more of the following:

[0383] (i) Basically similar to Fig.37 The XRPD pattern depicted in (bottom spectrum);

[0384] (ii) a DSC graph showing thermal events at about 99.9° C. and / or about 328° C.;

[0385] (iii) substantially similar to Fig.38 and / or Fig.39 The DSC diagram depicted in ;

[0386] (iv) a TGA graph showing a weight loss of about 8.635% up to about 150°C; and

[0387] (v) Basically similar to Fig.38 and / or Fig.39 TGA diagram depicted in .

[0388] 51. The solid form of embodiment 15, wherein the solid form is Form S9-b.

[0389] 52. The solid form of embodiment 51, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-theta.

[0390] 53. The solid form of embodiment 51, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-theta.

[0391] 54. A solid form as described in embodiment 51, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all positions listed in Table S9-b.

[0392] 55. A solid form as described in embodiment 51, wherein the solid form is characterized by being substantially similar to Fig.37 (bottom spectrum) XRPD pattern depicted.

[0393] 56. The solid form of embodiment 15, wherein the solid form is Form S10.

[0394] 57. The solid form of embodiment 56, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-theta.

[0395] 58. A solid form as described in embodiment 56, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91 and about 15.53 degrees 2-θ.

[0396] 59. The solid form of embodiment 56, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all of the positions listed in Table S10.

[0397] 60. The solid form of embodiment 56, wherein the solid form is characterized by one or more of the following:

[0398] (i) Basically similar to Fig.40A The XRPD pattern depicted in;

[0399] (ii) a DSC graph showing thermal events at about 141.3° C., about 324° C., and / or about 336° C.;

[0400] (iii) substantially similar to Fig.40B The DSC diagram depicted in ;

[0401] (iv) a TGA graph showing a weight loss of about 16% up to about 150°C; and

[0402] (v) Basically similar to Fig.40B TGA diagram depicted in .

[0403] 61. The solid form of embodiment 15, wherein the solid form is Form S12 and / or Form S15.

[0404] 62. The solid form of embodiment 61, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-theta.

[0405] 63. The solid form of embodiment 61, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-theta.

[0406] 64. The solid form of embodiment 61, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S12 or Table S15.

[0407] 65. The solid form of embodiment 61, wherein the solid form is characterized by one or more of the following:

[0408] (i) Basically similar to Fig.42 The XRPD pattern depicted in;

[0409] (ii) a DSC graph showing thermal events at about 80.8°C, about 180°C, and / or about 332°C;

[0410] (iii) substantially similar to Fig.43 The DSC diagram depicted in ;

[0411] (iv) a TGA graph showing a weight loss of about 4.448% up to about 150°C; and

[0412] (v) Basically similar to Fig.43 TGA diagram depicted in .

[0413] 66. The solid form of embodiment 15, wherein the solid form is Form S13.

[0414] 67. The solid form of embodiment 66, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-theta.

[0415] 68. The solid form of embodiment 66, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-theta.

[0416] 69. The solid form of embodiment 66, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S13.

[0417] 70. The solid form of embodiment 66, wherein the solid form is characterized by one or more of the following:

[0418] (i) Basically similar to Fig.44 and / or Fig.53 The XRPD pattern depicted in;

[0419] (ii) a DSC graph showing thermal events at about 55.4°C, about 148.8°C, about 191.8°C, and / or about 335°C;

[0420] (iii) substantially similar to Fig.45 The DSC diagram depicted in ;

[0421] (iv) a TGA graph showing a weight loss of about 6.162% up to about 180°C; and

[0422] (v) Basically similar to Fig.45 TGA diagram depicted in .

[0423] 71. The solid form of embodiment 15, wherein the solid form is Form S14.

[0424] 72. The solid form of embodiment 71, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-theta.

[0425] 73. The solid form of embodiment 71, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-theta.

[0426] 74. The solid form of embodiment 71, wherein the solid form is characterized in that the peaks in its XRPD pattern are located at substantially all positions listed in Table S14.

[0427] 75. The solid form of embodiment 71, wherein the solid form is characterized by one or more of the following:

[0428] (i) Basically similar to Fig.46A The XRPD pattern depicted in;

[0429] (ii) a DSC graph showing thermal events at about 143.7° C. and / or about 331° C.;

[0430] (iii) substantially similar to Fig.46B The DSC diagram depicted in ;

[0431] (iv) a TGA graph showing a weight loss of about 15.84% up to about 180°C; and

[0432] (v) Basically similar to Fig.46B TGA diagram depicted in .

[0433] 76. A pharmaceutical composition comprising the solid form of any one of embodiments 1-75 and a pharmaceutically acceptable carrier.

[0434] 77. The pharmaceutical composition of embodiment 76, wherein the pharmaceutical composition is a solid.

[0435] 78. The pharmaceutical composition of embodiment 76 or 77, wherein the pharmaceutical composition is formulated for oral administration.

[0436] 79. A pharmaceutical composition prepared by a method comprising the steps of: providing a solid form as described in any one of embodiments 1-75; and formulating the solid form with a suitable excipient to provide a pharmaceutical composition.

[0437] 80. A pharmaceutical composition comprising:

[0438] a first portion comprising a bile acid or a salt thereof, wherein the first portion is configured for immediate release in the colon of a subject;

[0439] a second portion adjacent to the first portion, the second portion comprising a bile acid or a salt thereof, and wherein the second portion is configured for extended release in the colon of the subject; and

[0440] Degradable or erodible coatings associated with pharmaceutical compositions,

[0441] wherein at least one of the first part and the second part comprises a solid form as described in any one of embodiments 1-75.

[0442] 81. A pharmaceutical composition comprising:

[0443] a first portion comprising a bile acid or a salt thereof, wherein the first portion is configured for immediate release in the colon of a subject;

[0444] a second portion adjacent to the first portion, the second portion comprising a bile acid or a salt thereof, and wherein the second portion is configured for extended release in the colon of the subject; and

[0445] Degradable or erodible coatings associated with pharmaceutical compositions,

[0446] The pharmaceutical composition is prepared by a method comprising the following steps:

[0447] Providing a solid form as described in any one of embodiments 1-75; and

[0448] Solid forms are formulated with suitable excipients to provide pharmaceutical compositions.

[0449] 82. The pharmaceutical composition of embodiment 80 or 81, wherein the pharmaceutical composition is a tablet.

[0450] 83. The pharmaceutical composition of any one of embodiments 80-82, wherein the bile acid or salt thereof in the first part and the second part is chenodeoxycholic acid or a salt thereof.

[0451] 84. A pharmaceutical composition as described in embodiment 83, wherein the first part and the second part comprise a solid form as described in any one of embodiments 1-75.

[0452] 85. The pharmaceutical composition of any one of embodiments 80-84, wherein the coating is or comprises Eudragit S100.

[0453] 86. A method comprising administering to a subject in need thereof the solid form of any one of embodiments 1-75 or the pharmaceutical composition of any one of embodiments 76-85.

[0454] 87. The method of embodiment 86, comprising orally administering a solid form of any one of embodiments 1-75 or a pharmaceutical composition of any one of embodiments 76-85.

[0455] 88. A method of treating a disease, disorder, or condition comprising administering to a subject in need thereof a solid form of any one of embodiments 1-75 or a pharmaceutical composition of any one of embodiments 76-85.

[0456] 89. The method of any one of embodiments 86-88, wherein the subject suffers from a gastrointestinal disease, disorder, or condition.

[0457] 90. The method of any one of embodiments 86-88, wherein the subject suffers from constipation.

[0458] 91. The method of any one of embodiments 86-88, wherein the subject has irritable bowel syndrome with constipation (IBS-C).

[0459] 92. A method of preparing a solid form of any one of embodiments 1-75 according to the methods described herein.

[0460] 93. A method of preparing a solid form as described in any one of embodiments 1-14, wherein the method comprises the following steps:

[0461] providing chenodeoxycholic acid; and

[0462] Contact chenodeoxycholic acid with a suitable base in a suitable solvent

[0463] To provide a solid form.

[0464] 94. The method of embodiment 93, wherein the suitable base is sodium hydroxide.

[0465] 95. A method as described in embodiment 93, wherein the suitable solvent is selected from methyl isobutyl ketone, n-butanol and water.

[0466] 96. A method of preparing a solid form as described in any one of embodiments 2-6, wherein the method comprises the following steps:

[0467] providing a mixture of chenodeoxycholic acid in methyl isobutyl ketone;

[0468] adding aqueous sodium hydroxide to the mixture;

[0469] heating the mixture; and

[0470] The solvent was removed to afford a solid form.

[0471] 97. A method of preparing a solid form as described in any one of embodiments 7-11, wherein the method comprises the following steps:

[0472] providing a mixture of chenodeoxycholic acid in n-butanol;

[0473] Adding aqueous sodium hydroxide to the mixture;

[0474] heating the mixture; and

[0475] The solvent was removed to afford a solid form.

[0476] 98. The method of embodiment 96 or 97, wherein the mixture is heated to azeotropic reflux.

[0477] 99. A method for preparing a pharmaceutical composition as described in any one of embodiments 76-85, wherein the method comprises the following steps:

[0478] Providing a solid form as described in any one of embodiments 1-75; and

[0479] Formulate solid forms with suitable excipients

[0480] To provide a pharmaceutical composition.

[0481] Example

[0482] The examples provided herein record and support certain aspects of the present disclosure, but are not intended to limit the scope of any claim. The following non-limiting examples are provided to further illustrate certain teachings provided by the present disclosure. According to the application, it will be understood by those skilled in the art that various changes may be made to the specific embodiments described in the present example without departing from the spirit and scope of this teaching.

[0483] Materials and Methods - Examples 1-4

[0484] X-ray powder diffraction (XRPD)

[0485] XRPD analyses were run on a Bruker D8 Advance diffractometer with a goniometer radius of 280 mm and operating in Bragg-Brentano geometry. The radiation used was Ni-filtered CuKα The detector used was a silicon strip (LynxEye) detector. The range of analysis was 2θ 3-40° with a step size of 0.02°. The sample holder used was a zero-background silicon single crystal. The acquired data were analyzed using Diffrac.Eva software version 4.3.0.1 (Bruker AXS).

[0486] Differential Scanning Calorimetry (DSC)

[0487] Differential Scanning Calorimetry (DSC) analysis was run on a Mettler-Toledo DSC-3 unit. Accurately weighed 3-7 mg samples were placed in an aluminum pan with a perforated lid and heated from 30° C. to 300° C. at 10° C. / min under a nitrogen flow. The data obtained were analyzed using Stare software version 16.00.

[0488] Thermogravimetric analysis (TGA)

[0489] Thermogravimetric analysis (TGA) was run on a Mettler-Toledo TGA2. Accurately weighed 15-30 mg samples were heated at 10°C / min from 25°C to 300°C under a nitrogen flow. The data obtained were analyzed using Stare software version 16.20.

[0490] Dynamic Vapor Sorption (DVS)

[0491] DVS measurements were performed using SMS-DVS Intrinsic. The sample size was about 50 mg and was accurately weighed. The measurements were performed at 25 °C and the relative humidity (RH) range investigated was 40-90-0-90% RH with a step size of 10% RH. After each RH change, the mass of the sample was allowed to stabilize (waiting time from 10 to 60 minutes, stability criterion ≤ 0.002 g for 10 minutes).

[0492] The hygroscopicity of the sample is calculated as follows:

[0493] Weight change % = (W2-W1)W1 / ·100

[0494] in:

[0495] W1: Sample weight at the beginning of the experiment (25°C and 40% RH)

[0496] W2: Sample weight at 25 °C and 80% RH in the first adsorption cycle

[0497] High pressure liquid chromatography (HPLC)

[0498] For intrinsic dissolution studies, the following HPLC method was used:

[0499]

[0500]

[0501] Example 1. Preparation and characterization of provided solid forms

[0502] Sodium chenodeoxycholate Form A

[0503] NaCDC Form A was prepared according to the following exemplary procedure: CDCA (50 g) and methyl isobutyl ketone (2500 mL, 5 volumes) were loaded at 20°C ± 5°C in a one-liter reactor equipped with a dean-stark apparatus. The mixture was stirred and then 18.7 g of a 30% p / p solution of NaOH in water was added. Once the dissolution was complete, a slight exothermic reaction was observed. The solution was heated under azeotropic reflux for 2 to 3 hours to distill off water. Once crystallization began to occur, the mixture was stirred for another hour at 115-117°C, then cooled at 20°C ± 5°C and stirred at 20°C ± 5°C for 2 hours. The mixture was filtered by washing the panel with 50 mL of methyl isobutyl ketone. The wet product (51.6 g) was vacuum dried at 50°C to obtain NaCDC Form A (47.8 g, 85.2% yield).

[0504] The XRPD pattern of Form A is shown in Figure 1 , and the corresponding data are summarized as follows:

[0505]

[0506]

[0507] like Figure 2 As shown, DSC analysis of Form A shows water loss starting from slightly above ambient temperature and continuing to about 150°C. Karl-Fischer analysis shows a 6.0 w / w% water content of Form A. TGA analysis of Form A ( Figure 3 ) showed a weight loss of 4.3% up to 150° C. Form A was determined to be a sesquihydrate.

[0508] DVS of Form A showed that it was hygroscopic (14.1% weight change in the first adsorption cycle, Fig. 9 ).

[0509] Exposure to humid air resulted in an increase in the water content of Form A, ultimately leading to partial amorphization and loss of crystallinity after 15-20 hours at 95% humidity ( Figure 4 ).

[0510] Sodium chenodeoxycholate form B

[0511] NaCDC Form B was prepared according to the following exemplary procedure: CDCA (50 g) and n-butanol (300 mL) were loaded at 20°C ± 5°C in a one-liter reactor equipped with a Dean-Stark apparatus. The mixture was stirred and then NaOH solution (18.7 g, 30% p / p aqueous solution) was added. The solution was heated under azeotropic reflux for 3-4 hours. Once crystallization began to occur, approximately 200 mL (4 volumes) of solvent was distilled over approximately 3-4 hours until a vapor temperature of 117°C was reached. The resulting suspension was cooled to 20°C ± 5°C and shaken at 20°C ± 5°C for 1 hour. The solid was filtered and washed with n-butanol (50 mL). The wet solid was vacuum dried at 75°C to obtain NaCDC Form B (46.7 g, 88.5% yield).

[0512] The XRPD pattern of Form B is Figure 5 , and the corresponding data are summarized as follows:

[0513]

[0514]

[0515] like Figure 6 As shown, DSC analysis of Form B showed no thermal events from room temperature to a broad melting event starting at about 288°C. Karl-Fischer analysis showed a water content of <0.1 w / w% for Form B. TGA analysis of Form B ( Figure 7 ) showed a weight loss of <0.1% up to 150° C. Form B was determined to be an anhydrate.

[0516] DVS of Form B showed that it was slightly hygroscopic (0.8% weight change in the first adsorption cycle, Fig.10 ).

[0517] Exposure to moist air leads to final amorphization after 15-20 hours at 95% humidity ( Figure 8 ), but the loss of crystallinity is significantly slower than that of Form A.

[0518] Example 2. Stability study

[0519] The in-process stability of NaCDC Form B was evaluated under two conditions at reflux, as described below in Table 1. No changes in the HPLC impurity profile were observed under either condition, indicating that the product is stable under these conditions.

[0520] Table 1

[0521]

[0522]

[0523] Example 3. Intrinsic dissolution study

[0524] The intrinsic dissolution profiles of NaCDC Form A and Form B were determined from constant surface area drug disks using a USP spinning disk apparatus in phosphate buffer (pH 7.4) at 37° C. After compression (described below), no changes in the solid form were observed based on XRPD.

[0525] A typical device consists of a punch and a die, with the base of the device attached to a surface plate. The die has a cavity in which a defined amount of material for which the intrinsic dissolution rate is to be determined is placed. The punch is then inserted into the die cavity and the test material is compressed with a hydraulic press. A non-disintegrating compact of the material is formed in the die cavity, having a single face of a defined area exposed on the bottom of the die. The die assembly is then attached to a shaft with a bracket and the surface plate is removed. The shaft holding the die assembly is positioned in the dissolution medium at a distance of not less than 1.0 cm from the bottom of the container. In this procedure, fluid flow is generated by the rotation of the die. The amount of material dissolved over time is measured. Specifically, the cumulative amount dissolved at each time point is corrected for losses due to sampling. If the amount vs. time curve shows curvature, only the initial linear portion of the curve is used to determine the dissolution rate. The method parameters are summarized as follows:

[0526] Device Rotating disk device (USP) Surface Area <![CDATA[0.5024cm 2 (diameter = 0.8cm)]]> Compression force 2 tons for 2 minutes Amount of material 150mg Dissolution medium USP Phosphate Buffer pH 7.4, 500mL Dissolution medium temperature 37℃±0.5℃ Rotation speed 100rpm±0.5rpm Sample volume 2mL Filters Whatman 0.45μm TF filter

[0527] The intrinsic dissolution profiles of NaCDC Form A and Form B are shown in Fig.11 The linear regression analysis of the curve is shown in Fig.12 The intrinsic dissolution rates are summarized in Table 2. Notably, Form B has a higher intrinsic dissolution rate than Form A while having lower hygroscopicity.

[0528] Table 2

[0529] form <![CDATA[IDR(mg·min -1 ·cm -2 )]]> A 0.6959 B 0.9218

[0530] Example 4. Solubility curve measurement

[0531] Solubility curves of NaCDC Form A and Form B were measured using a Crystal 16 automatic crystallizer (Technobis Crystallization Systems), which has an array of 16 microreactors equipped with a turbidimeter for determining clearing and cloud points. Four samples of different concentrations of each crystal form were prepared by accurately weighing different amounts of each sample and adding 1000 μL of phosphate buffer (pH 7.4) to each vial. The suspension thus obtained was stirred with a magnetic stirrer and heated from 0°C to 90°C at 0.5°C / min. The clearing point of each sample was determined and plotted to obtain a crystallization curve ( Fig.13 ). Compared with NaCDC Form A, NaCDC Form B showed higher solubility.

[0532] Materials and Methods - Examples 5-10

[0533] X-ray powder diffraction (XRPD)

[0534] XRPD analysis was performed using a Bruker D8 Discover diffractometer with DAVINCI configuration, scanning the sample between 1.5 and 45° 2θ angles in transmission mode (scan type: 2θ or offset coupled 2θ / θ), and using an acquisition time of 7.58 minutes (0.01° per step increment, 0.1 s per step time, and 40 mA / 40 kV generator voltage / generator current to achieve 1.6 kW power). Approximately 2-3 mg was used for each sample. The detection limit of XRPD varies based on the crystallinity of the sample. In general, for crystalline compounds, it is estimated that the detection limit of XRPD is about 2 wt % or even lower.

[0535] Differential Scanning Calorimetry (DSC)

[0536] About 3.9 mg of sample was weighed into an aluminum DSC pan and sealed non-hermetically with an aluminum lid. The sample pan was then loaded into a Setaram DSC131 EVO (equipped with a cooler). Once a stable heat flow response was obtained, the sample and reference were heated to 450°C at a rate of 10°C / min and the resulting heat flow response was monitored. Nitrogen was used as the purge gas with a flow rate of 40 cm 3 / min. Before analysis, the instrument was calibrated for temperature and heat flow using lead and indium reference standards. Sample analysis was performed with the help of CALISTO software, where the temperature of the thermal event was referenced as the starting temperature, measured according to the manufacturer's specifications.

[0537] Thermogravimetric analysis coupled with DSC (TG / DSC)

[0538] About 1.56 to 5.78 mg of sample was weighed into an open aluminum pan and loaded into a simultaneous SetaramLABSYS EVO thermogravimetric / differential scanning calorimeter (TG-DTA / DSC) and kept at 30°C for 15 minutes. The sample was then heated from 30°C to 550°C at a rate of 10°C / min, during which the change in sample weight and any differential thermal events were recorded. Nitrogen was used as the purge gas with a flow rate of about 180 cm 3 / min. Before analysis, the instrument was calibrated for mass loss and temperature using copper sulfate pentahydrate and indium and lead reference standards. Sample analysis was performed with the help of CALISTO software, where the corresponding mass loss and the temperature of the thermal event were referenced as the onset temperature, measured according to the manufacturer's specifications. All analyses were performed at a heating rate of 10°C / min and background was subtracted.

[0539] High performance liquid chromatography (HPLC)

[0540] HPLC analysis was performed on an Agilent 1260 Infinity chromatograph using a Hichrom C18 column 100 x 4.6 mm, 3.5 μm at 40°C. The method details are as follows:

[0541]

[0542] Example 5. Additional Characterization of NaCDC Form B

[0543] like Fig.14 As shown, an additional independent DSC analysis of NaCDC Form B was performed. This analysis revealed two endothermic events, one associated with a possible melting accompanied by a phase transition (T 起始 =291.9°C) and another one related to possible melting (T 起始 =331.6℃) related.

[0544] TG / DSC analysis of NaCDC Form B was also performed and the results are shown in Fig.15 This analysis revealed two endothermic events, one associated with a possible melting accompanied by a phase transition (T 起始 = 291.8 °C and heat = 35 J / g), and another one related to possible melting (T 起始 =336.4°C and heat =51.2 J / g). T between independent DSC analysis and TG / DSC analysis 起始 The difference is attributed to the difference in the type of crucible used (TG / DSC uses an open 100 μL aluminum crucible, while the stand-alone DSC uses a closed perforated 30 μL aluminum crucible).

[0545] Based on the results obtained from TG / DSC analysis, a sample of NaCDC Form B was heated at 315° C. and another sample was heated at 360° C. After heating, the samples were cooled to room temperature and analyzed by XRPD ( Fig.16 ). The sample heated at 315°C had a different diffraction pattern than the starting material. The material obtained after heating at 360°C was amorphous. HPLC analysis showed that the sample heated at 315°C had a purity of 66.9%.

[0546] Example 6. Photostability study

[0547] The photostability of NaCDC Form B in solid state and MeOH solution was evaluated by exposing it to UV 254nm light for 48 hours in a transparent, amber and foil wrapped vial. The solution was prepared by weighing about 10mg NaCDC Form B and mixing it with 500μL MeOH. The solid and solution were sampled after 48 hours and analyzed by HPLC to evaluate degradation. At the same time, XRPD analysis was performed on the recovered solid. The experimental results are summarized in Table 3.

[0548] Table 3

[0549]

[0550]

[0551] SM = starting material (i.e. NaCDC Form B)

[0552] In experiments performed in the solid state, no form transitions were observed by XRPD, indicating that NaCDC Form B is stable ( Fig.17 In solution, HPLC analysis indicated that the compound was stable as evidenced by minimal loss of purity (see Table 3).

[0553] Example 7. Stability study in slurry / solution

[0554] The NaCDC Form B of about 10mg is weighed into a transparent HPLC vial, and the solvent (500 μL) of selection is added into the vial. Experiments ST07, 09, 11, 13, 15, 17, 19 and 21 are continuously stirred for 24h at 30 ℃ and 60 ℃, and sampling is used for HPLC analysis after 4h and 24h simultaneously. Subsequently, identical experiments are evaporated at 30 ℃ for 24h under reduced pressure (21-22mbar), and solid is assessed by HPLC and XRPD. Respectively, solutions and slurries from experiments ST10, 12, 14, 16, 18, 20 and 22 are stirred for 24h (not sampled) at 30 ℃ and 60 ℃, and evaporated at 60 ℃ for 24h under reduced pressure (20-21mbar). The material sampling recovered is analyzed for HPLC and XRPD. Experimental results are summarized in Table 4.

[0555] Table 4

[0556]

[0557]

[0558] Am. = amorphous; evap. = evaporated; SM = starting material (ie NaCDC form B); PO = preferred orientation

[0559] XRPD analysis indicated that NaCDC Form B was stable, as no form transitions were observed in most slurry experiments. Two exceptions were observed, namely ST19 and ST20 (in MEK evaporated at 30°C and 60°C, respectively), and they gave rise to a new Form S1 ( Fig.18 ).

[0560] In general, under the test conditions, the starting material remains stable in solution and / or slurry. The HPLC analysis performed throughout the stability test revealed a purity of ≥86.1% at 212nm, except for ST08 and ST16 experiments (evaporated at 60°C), in which the purity was reduced to about 84.5%. In addition, experiments ST19 and ST21 (using MEK and evaporating at 30°C) showed lower purities (74.1% and 55.9%), which may indicate the presence of amorphous impurities that cannot be detected by XRPD.

[0561] Characterization of Form S1

[0562] Form S1 was obtained from experiments ST19 and ST20 (24 h in MEK slurry at RT and evaporated at 30° C. and 60° C., respectively).

[0563] The samples from ST19 were characterized by XRPD as Fig.19A The corresponding data are summarized in Table S1-A:

[0564] Table S1-A

[0565]

[0566] The samples from ST20 were characterized by TG / DSC, as Fig.19B As shown. Three endothermic events were found in the DSC trace: the first event was related to the desolvation process, where T 起始 =96.0 °C and the mass loss is 2.177% (3.704% of the theoretical mass corresponds to 0.25 MEK molecules). Therefore, the mass loss can be attributed to physical adsorption or residual adsorption. Considering the preferred orientation of the measured sample, the second event corresponds to an artifact or a phase transition, where T 起始 =142.5°C and 3.29 J / g of heat. The third event corresponds to the melting process of the form, where T 起始 = 313.4° C. The sample from ST19 showed a similar TG / DSC trace, although it did not show the second endotherm observed from ST20.

[0567] Example 8. Solubility study

[0568] About 10mg of NaCDC Form B is weighed into 1.6mL HPLC vials. A cylindrical magnetic stirring bar covered with 3-5mm PTFE is added to the vial. By adding a small continuous aliquot of each selected solvent system to the corresponding vial, stirring at RT, a qualitative solubility evaluation study is carried out at intervals of about 15 minutes (at 500rpm, 50μL volume is added to 200μL; at 700rpm, 100μL volume is added to the total volume between 200 and 1000μL). The vial is visually inspected before each addition to check the dissolution of the starting material, and the solvent addition is stopped when complete dissolution is observed. The transparent solution is placed and left to stand at RT. When the total volume of 1mL is reached and dissolution (concentration of about 10mg / mL at RT) does not occur, the vial is heated under stirring, first heated at 40°C (except for the experimental SAS23 that uses ether to heat only at 30°C for 1h), and then heated at 50°C. The experiment was kept for 1 h at each temperature and then visually inspected to see if dissolution occurred. During the experimental time, the magnetic stirring bar was removed and all slurries or solutions were dried at different temperatures according to the boiling point of each solvent used (i.e., dried for 21 hours at 30 ° C, 20-21 mbar or 50 ° C, 21 mbar; except for experiments SAS07, SAS33, SAS34, SAS35, SAS36 and SAS45 dried for 43 hours at 50 ° C). All resulting solids were analyzed by XRPD. For several selected experiments, HPLC analysis was carried out. The solids that obtained new XRPD patterns were studied by TGA / DSC. The results are summarized in Table 6, and the description of qualitative solubility terms is provided in Table 5.

[0569] Table 5

[0570] Descriptive terms Volume of solvent required for 1 compound (about 10 mg) (10 μL) Very soluble Less than 5 Soluble 5 to 10 Dissolve 10 to 30 Slightly soluble 30 to 100 Slightly soluble More than 100, dissolves at 30 / 40℃ or 50 / 60℃ Insoluble More than 100, insoluble at 30 / 40℃ or 50 / 60℃

[0571] Table 6

[0572]

[0573]

[0574]

[0575]

[0576] Am. = amorphous; SM = starting material (i.e. NaCDC Form B); PO = preferred orientation; pks. = peak; Evap.Cond.: A = 30°C, low pressure (final value = 20-21 mbar) for 21 hours; B = 50°C, low pressure (final value = 21 mbar) for 21 hours; C = 50°C, low pressure (final value = 21 mbar) for 43 hours

[0577] Most of the solids tested showed good purity by HPLC, but 2-ethoxyethanol, 3-methyl-1-butanol, benzonitrile, DMAc, NMP, DMSO, and H 2 The exception was the experiment with O:DMSO (1:1 v / v), where the purity dropped from 99.2% to 1.2-68.0%.

[0578] XRPD analysis revealed the formation of several new forms, such as Fig. 20 shown.

[0579] Characterization of Form S2

[0580] Form S2 was identified from experiments using EtOH (SAS03) or an equal volume mixture of EtOH with MeCN (SAS39) and n-heptane (SAS48). Based on TG / DSC analysis of experiment SAS39 ( Fig.21A ), Form S2 was assigned as the solvated form with the first endothermic event indicating desolvation at 112.9 °C with a mass loss of 3.95% (attributed to 0.5 EtOH molecules, corresponding to 5% of theoretical mass). The second event represented a T of 177.8 °C. 起始 The phase transition at 195°C was followed by a recrystallization event at about 195°C and finally at 334.1°C (T 起始 ) is melted.

[0581] Characterization of Form S3

[0582] Form S3 was identified from a single experiment with 2-ethoxyethanol (SAS07). Based on HPLC analysis (38% purity at 212 nm), it was determined that Form S3 was likely a mixture of major crystalline degradation products and NaCDC. XRPD analysis of material from experiment SAS07 is shown in Fig. 21B , and the corresponding data are summarized in Table S3:

[0583] Table S3

[0584]

[0585]

[0586] Characterization of Form S4

[0587] The S4 form was identified from a single experiment with 2,2,2-trifluoroethanol (SAS08). Based on TG / DSC analysis of the SAS08 experiment ( Fig. 22 ), Form S4 was assigned as the solvated form with the first endothermic event indicating desolvation at 146.5 °C with a mass loss of 14.23% (attributed to 1 TFE molecule, corresponding to 19.44% of theoretical mass). The second event represented desolvation at 333.9 °C (T 起始 ) is melted.

[0588] Characterization of Form S5

[0589] Form S5 was identified from two experiments using equal volumes of MeOH mixtures with EtOAc (SAS46) and n-heptane (SAS47). The XRPD spectrum of the material obtained from experiment SAS47 is shown at Fig.23A , and the corresponding data are summarized in Table S5-A:

[0590] Table S5-A

[0591]

[0592]

[0593] Based on TG / DSC analysis of experimental SAS47 ( Fig. 23B ), Form S5 was assigned as the solvated form with the first endothermic event indicating desolvation at about 82 °C with a mass loss of 4.79% (attributed to 0.5 MeOH molecules, corresponding to 3.59% of theoretical mass). The second event represented a T of 183.9 °C. 起始 and finally at 331.5℃ (T 起始 ) is melted.

[0594] Example 9. Polymorph Screening

[0595] Slurry

[0596] About 15mg of NaCDC Form B is weighed into an HPLC vial, and an appropriate volume of solvent is added at RT. The slurry is aged for 7 days at multiple temperatures (5°C, 25-30°C, 40°C and 50°C) under stirring (500rpm). All solids are air-dried on filter paper and then analyzed by XRPD. According to the results obtained by XRPD and the availability of materials, some experiments are analyzed by HPLC and TG / DSC. The results from the slurry experiments are summarized in Table 7.

[0597] Table 7

[0598]

[0599]

[0600]

[0601]

[0602]

[0603]

[0604]

[0605]

[0606] Am. = amorphous; SM = starting material (ie, NaCDC Form B); PO = preferred orientation; pks. = peak

[0607] Based on XRPD data, most of the material recovered from the slurry experiments recovered the same crystalline phase as the starting material (NaCDC Form B). In some experiments, three different forms were identified, namely Form S1 (or a form isostructural to Form S1), Form S2, and Form S7.

[0608] Characterization of Form S1

[0609] Form S1 (or a form similar to and / or isostructural to Form S1) was obtained from experiments SL13 and SL39 with tert-butyl methyl ether at 5°C and 25-30°C, respectively. HPLC analysis of both materials showed good purity, 87.2% (SL13) and 84.0% (SL39) at 212 nm. XRPD analysis of these samples is shown at Fig.24A , and the corresponding data for samples from experiment SL39 are summarized in Table S1-B:

[0610] Table S1-B

[0611]

[0612]

[0613] TG / DSC analysis of SL39 (air-dried on filter paper for at least 2 h before thermal analysis) showed two endothermic events ( Fig. 24B ): The first event is related to the desolvation process, where T 起始 =93.2 °C and a mass loss of 1.241% (2.19% of the theoretical mass corresponds to 0.125 MTBE molecules). Therefore, the observed mass loss can be attributed to physical adsorption or residual adsorption. The second event corresponds to the melting of the form, where T 起始=312.8℃.

[0614] Characterization of Form S2

[0615] Form S2 was obtained from all slurry experiments involving ethanol (i.e., experiments SL01, SL26, and SL52 at 5°C, 25-30°C, and 40°C, respectively) or from mixtures with ethanol at 5°C, 25-30°C, and 50°C (experiments SL22, SL48, and SL74 using EtOH:MeCN 1:1 v / v, respectively, and experiments SL23, SL49, and SL75 using EtOH:n-heptane 1:1 v / v, respectively).

[0616] TG / DSC analysis of the material obtained from experiment SL26 ( Fig.25 ) shows two endothermic events: the first event is associated with desolvation, where T 起始 =113.4°C and a mass loss of 7.013% (5% of theoretical mass corresponds to 0.75 EtOH molecules). The second event is attributed to melting, which has T 起始 = 324.6°C. The presence of two maximum temperatures associated with melting can be attributed to the inhomogeneity of the material (eg, a possible mixture of small and large particles). Based on the data obtained, Form S2 was assigned to be a solvate of NaCDC.

[0617] Characterization of Form S7

[0618] Form S7 was obtained from experiments SL27 and SL56 with 2-PrOH at 25-30°C and 50°C, respectively. The XRPD spectra of the materials obtained from experiments SL27 and SL56 are shown in Fig.26A , and the corresponding data from experiment SL56 are summarized in Table S7:

[0619] Table S7

[0620]

[0621]

[0622] Based on TG / DSC analysis of the material obtained from experiment SL56 (air dried on filter paper for at least 2 h before thermal analysis), three endothermic events were observed ( Fig.26B ). The first event is attributed to desolvation, where T 起始 =109.2°C and a mass loss of 10.037% (12.66% of the theoretical mass corresponds to one 2-PrOH molecule). The second event may correspond to a phase transition (T 起始 =324.5°C and 2.65 J / g of heat). The third event represents melting, where T 起始= 335.3°C. Based on the similar melting temperature (T 起始 =336.4°C and Max T =340.2°C), Form S7 was assigned as a solvated form of anhydrous NaCDC Form B.

[0623] Ultrasonic treatment of slurry

[0624] About 15 mg of NaCDC Form B was weighed into an HPLC vial, and 0.4 mL of the corresponding solvent was added at RT. The slurry was ultrasonically treated for 15 minutes, then cooled at 5 ° C for 30 minutes, and this cycle was repeated 6 times. At the end of the sixth cycle, all experiments were air-dried on filter paper, and the solid recovered was analyzed by XRPD. Based on XRPD data, some experiments were analyzed by HPLC. The results of the slurry from ultrasonic treatment and thermal cycle experiments (SLS) at 5 ° C are presented in Table 8.

[0625] Table 8

[0626]

[0627] SM = starting material (i.e. NaCDC form B); PO = preferred orientation; pks. = peak

[0628] Based on XRPD data, most of the materials recovered from the slurry experiments recovered the same crystalline phase as the starting material (NaCDC Form B). Form S2 was obtained from experiments SLS08 and SLS09 with EtOH:MeCN 1:1 v / v and EtOH:n-heptane 1:1 v / v, respectively. HPLC analysis of both materials showed good purity, 79.2% (SLS08) and 89.7% (SLS09) at 212 nm.

[0629] Slow evaporation

[0630] Five stock solutions (containing MeOH, water, 2,2,2-trifluoroethanol, MeOH:EtOAc (1:1 v / v) and MeOH:acetone (1:1 v / v)) were prepared with NaCDC Form B at RT. The final concentration of each solution was close to the concentration obtained from the solubility study described in Example 8. About 19-23 mg of NaCDC Form B was weighed into a 1.6 mL HPLC vial (or in the case of stock solutions containing MeOH:EtOAc and MeOH:acetone, weighed into an 8 mL flask) and dissolved in the appropriate solvent at RT. In the case of stock solutions containing water, about 40 mg of NaCDC Form B was used. The experiment was stirred continuously (500 rpm) for 1 h at RT, and then the solution was filtered with a 0.45 μm PTFE filter. During the filtration of the stock solution with water, foaming was observed, so the filtration should be performed slowly and in several steps. The filtered solution was then slowly evaporated at 25°C (experiments EV01-05) or 50°C (experiments EV06-09) under atmospheric pressure. After complete evaporation of the solvent, the solid was recovered and analyzed by XRPD. Depending on the results obtained from XRPD and the availability of the material, some experiments were analyzed by HPLC and TG / DSC. The results from slow evaporation crystallization (EV) are summarized in Table 9.

[0631] Table 9

[0632]

[0633]

[0634] Am. = amorphous; lc = low crystallinity; SM = starting material (i.e. NaCDC form B); PO = preferred orientation; pks. = peak

[0635] Based on XRPD data, most of the material recovered from these experiments was in the amorphous phase.In some experiments, four different forms were identified, namely Form S1 (or forms isomorphous to Form S1), Form S4, Form S5 and Form S6.

[0636] Characterization of Form S1

[0637] Form S1 (or a form similar to and / or isostructural to Form S1) was obtained from Experiment EV03 with 2,2,2-trifluoroethanol at 25-30°C. HPLC analysis of the material showed a good purity of 88.3% at 212 nm. TG / DSC analysis of the material obtained from Experiment EV03 showed three endothermic events ( Fig. 27 ). The first two events were attributed to desolvation, and T 起始 =94.4℃ and T 起始=144.7°C, and the cumulative mass loss is 5.487% (4.86% of the theoretical mass corresponds to 0.25 TFE molecules). The third event corresponds to the melting of the form, where T 起始 =335.9℃.

[0638] Characterization of Form S4

[0639] Form S4 (mixture with SM and preferred orientation) was obtained from experiment EV07 after slow evaporation with TFE at 50°C. The material had a purity of 91.7% as judged by HPLC at 212 nm. From experiments with TFE, the results indicated that Form S4 was a solvated form.

[0640] Characterization of Form S5

[0641] Form S5 was obtained from Experiment EV09 with MeOH:acetone 1:1 v / v at 50°C. Based on TG / DSC analysis of the material obtained from Experiment EV09, two events were observed ( Fig.28 ). Prior to the first event, a mass loss of 5.642% was observed on the TG curve, which is not attributable to a well-defined desolvation process. This could be due to physically adsorbed solvent (theoretical mass was calculated to be 7.17% for 1 MeOH molecule). A possible recrystallization event was observed, with T 起始 =195.3°C (and 2 highest temperatures at 198.9°C and 212.5°C). Melting events were observed with T 起始 =332.9℃.

[0642] Characterization of Form S6

[0643] Form S6 was obtained from Experiment EV08 with MeOH:EtOAc 1:1 v / v at 50°C. Form S6 is similar to Form S3 from SAS07 experiment. The HPLC purity of the material was determined to be 71.4% at 212 nm (with 18% of the major impurity at a retention time of 3.81 minutes). Based on TG / DSC analysis of the material obtained from Experiment EV08, three events were observed ( Fig.29 ). The first broad endothermic event is associated with desolvation, which has T 起始 =50.6°C and a mass loss of 2.456% (2.191% of theoretical mass corresponds to 0.125 EtOAc molecules). The second exothermic event is associated with recrystallization (T 起始 =199.8°C), while the third endothermic event is associated with melting, which has T 起始 =331.5℃.

[0644] Solvent drop milling

[0645] The NaCDC Form B of about 20 mg was ground together with 10 μL aliquots of the corresponding solvent using an agate mortar with a pestle for 10 minutes at RT. When it was observed that the solvent evaporated completely, another aliquot of 10 μL solvent was added and this procedure was repeated until the experiment was completed. All solids were analyzed by XRPD. For the experiment of observing phase transition via XRPD, additional analysis of TG / DSC and / or HPLC was carried out. The results from the solvent drop grinding experiment (SDGR) are presented in Table 10.

[0646] Table 10

[0647]

[0648] lc = low crystallinity; SM = starting material (i.e. NaCDC Form B)

[0649] Based on the XRPD data, four new forms were identified: Form S1 (or isostructural to Form S1) (a mixture with NaCDC Form B), Form S2, Form S4, and Form S5.

[0650] Characterization of Form S1

[0651] Form S1 (or a form similar to and / or isostructurally to Form S1) was obtained from experiment SDGR02 with 2-PrOH as a mixture with NaCDC Form B. This material had a purity of 81.3% as judged by HPLC at 212 nm.

[0652] Characterization of Form S2

[0653] Form S2 was obtained from three experiments involving ethanol (SDGR01) or a mixture with ethanol (SDGR07-EtOH:MeCN 1:1 v / v and SDGR08-EtOH:n-heptane 1:1 v / v, respectively). The purity of the tested material was ≥86.5% at 212 nm as determined by HPLC (except for the material from experiment SDGR01, which had a purity of 83.4%).

[0654] Based on the TG / DSC analysis obtained from experiment SDGR01 ( Fig.30 ), Form S2 was assigned as the EtOH solvated form with the first endothermic event, indicating that at T 起始 =105.3°C with a mass loss of 7.677% (attributable to 0.75 EtOH molecules, corresponding to 5% of theoretical mass). The second event represents a T of 180.7°C. 起始 The phase transition at 200 °C was followed by a recrystallization event at about 200 °C and finally at 334.6 °C (T 起始) under the melting event. These results are similar to those obtained from the materials of experiments SAS48 and SDGR07.

[0655] Characterization of Form S4

[0656] Form S4 was obtained from experiment SDGR03 with TFE. The material showed a good HPLC purity of 90.9% at 212 nm. The results indicate that Form S4 is a TFE solvated form. The XRPD spectrum of the material obtained from experiment SDGR03 is shown at Fig.31A , and the corresponding data are summarized in Table S4:

[0657] Table S4

[0658]

[0659] Based on TG / DSC analysis of materials ( Fig.31B ), Form S4 may be solvated with TFE, and the first endothermic event indicates that 起始 =117.6°C with a mass loss of 14.620% (attributable to 1 TFE molecule, corresponding to 19.44% of theoretical mass). The second event represents a T of 185.4°C. 起始 The phase transition at 200 °C was followed by a recrystallization event at about 200 °C and finally at 335.6 °C (T 起始 ) Melting events occurred under . These results are similar to those obtained from experiment SAS08.

[0660] Characterization of Form S5

[0661] Form S5 was obtained from two experiments, namely SDGR05 with MeOH:EtOAc 1:1 v / v and SDGR06 with MeOH:acetone 1:1 v / v. The material had an HPLC purity of 87% at 212 nm. Based on the TG / DSC analysis obtained from experiment SDGR05 ( Fig.32A ), Form S5 is the solvated form with the first endothermic event, indicating desolvation at about 101°C, and a mass loss of 4.426% (attributable to 0.5 MeOH molecules, corresponding to 3.59% of theoretical mass). The second event represents a T of 190.9°C. 起始 and finally at about 333°C (T 起始 ) under which a melting event occurs.

[0662] Diffusion of vapor onto solid

[0663] About 20mg of NaCDC Form B is weighed into 1.6mL HPLC vials. Each of the above-mentioned vials is inserted separately into a 40mL container containing the corresponding solvent of initial 0.5mL. The container is isolated from light and atmosphere, and it is allowed to stand for 12 days in a closed cabinet at 25°C or in an oven at 50°C. After the experimental time, most of the samples still remain as solid / wet solid (experiment VDS02-12), and these samples are harvested and analyzed by XRPD. Experiment VDS01 produced a thin suspension after 12 days, and dried overnight at 30°C, 21mbar. All solids are analyzed by XRPD, and according to the result obtained, some experiments are also analyzed by HPLC and TG / DSC. The results from vapor diffusion to the solid (VDS) are summarized in Table 11.

[0664] Table 11

[0665]

[0666]

[0667] SM = starting material (i.e. NaCDC form B); PO = preferred orientation; pks. = peak

[0668] Based on XRPD data, most of the material recovered from these experiments was in the same crystalline phase as the starting material (NaCDC Form B). In addition, four different forms were identified, namely Form S2, Form S4, Form S5, and Form S8 (mixture with SM).

[0669] Characterization of Form S2

[0670] Form S2 was obtained from experiment VDS05 after diffusion with EtOH at 50°C for 12 days (and remained stable under RT storage conditions). The HPLC purity of the test material was 92.1% at 212 nm. The TG / DSC analysis of this material was consistent with the analysis obtained from experiments SAS48, SDGR01 and SDGR07. The XRPD analysis of this material is shown in Fig.33 , and the corresponding data are summarized in Table S2:

[0671] Table S2

[0672]

[0673]

[0674]

[0675] Characterization of Form S4

[0676] Form S4 was obtained from experiment VDS09 after diffusion with TFE at 50°C for 12 days (the suspension formed redissolved under RT storage conditions). The material had an HPLC purity of 90.9% at 212 nm.

[0677] Characterization of Form S5

[0678] Form S5 was obtained from experimental VDS01 after vacuum drying of a fine suspension produced after diffusion at RT for 12 days with MeOH. The HPLC purity of the material was about 90% at 212 nm. Based on TG / DSC analysis of VDS01 ( Fig.32B ), Form S5 was assigned as the solvated form with the first endothermic event indicating desolvation at about 101 °C with a mass loss of 4.426% (attributable to 0.5 MeOH molecules, corresponding to 3.59% of theoretical mass). The second event represented a T of 190.9 °C. 起始 The recrystallization event at about 333°C (T 起始 ) were observed under the conditions of

[0679] Characterization of Form S8

[0680] A mixture of Form S8 and the starting material (NaCDC Form B) was obtained from Experiment VDS12 after diffusion with MEK at 50°C for 12 days (and remained stable under RT storage conditions). The HPLC purity of the tested material was 93.7% at 212 nm. The XRPD spectrum of the material obtained from Experiment VDS12 compared to NaCDC Form B is shown in Fig.34A , and the corresponding data are summarized in Table S8:

[0681] Table S8

[0682]

[0683]

[0684] Based on the TG / DSC analysis of Experiment VDS12, three endothermic events were observed ( Fig.34B ). The first event is related to 起始 =292.6°C is related to the phase transition or melting process of form S8. A small second event is observed, which may indicate that T 起始 =322.4 °C, a phase transition or the presence of impurities (or attributable to the heterogeneity of the material) occurs. Finally, it is observed that at T 起始 = a melting event at 337.0° C. Considering that no mass loss was observed on the TG curve, Form S8 was assigned as the anhydrous form of NaCDC.

[0685] Antisolvent vapor diffuses into the solution

[0686] Three solutions (water: 203.41 mg / mL, MeOH: 100.37 mg / mL, and TFE: 50.66 mg / mL) were prepared with NaCDC Form B based on the solubility determined at RT in the solubility study of Example 8. The experiments were continued with stirring (500 rpm) for 1 h at RT until complete dissolution of the starting material, and then the solutions were filtered with a 0.45 μm PTFE filter (except for the water stock solution, which was filtered with a 0.2 μm nylon filter to avoid foaming encountered during EV experiments).

[0687] The concentrated solution of set volume is pipetted into a transparent HPLC vial, which is then inserted separately into a 40mL container containing an anti-solvent of 2mL. Each corresponding solvent is added as detailed in Table 12 below. The diffusion system is placed in a closed cabinet at 25°C or in an oven at 50°C for 12 days. After the experimental time, many samples have produced solids, which are harvested and analyzed by XRPD. The remaining solutions (ASDS01, 02, 05, 14, 17, 18 and 21) or suspensions (ASDS06) are dried overnight at 30°C, 21mbar. All recovered solids are analyzed by XRPD. Based on the results obtained, experiments were analyzed by HPLC. According to the availability of materials, some materials are selected for TG / DSC. The results from anti-solvent vapor diffusion into the solution (ASDS) are summarized in Table 12.

[0688] Table 12

[0689]

[0690]

[0691]

[0692]

[0693] Am. = amorphous; lc = low crystallinity; SM = starting material (ie, NaCDC Form B); PO = preferred orientation; pks. = peak; pp. = precipitate

[0694] Based on the XRPD results, eight different forms were identified from these experiments, namely Form S1 (or isomorphous to Form S1), Form S5, Form S9-a, Form S9-b, Form S10, Form S11 (or isomorphous to Form S3), Form S12 (as a mixture with an amorphous phase), Form S13 and Form S14.

[0695] Characterization of Forms S1 and S14

[0696] Form S1 (or a form similar and / or isostructural to Form S1) was obtained from experiments ASDS03 and ASDS07, respectively, after diffusion with water (and acetone as antisolvent) at 25° C. and 50° C. for 12 days. The HPLC purity of these materials was determined to be ≥89.1% at 212 nm.

[0697] The precipitate formed in the aqueous solution was stored at RT for up to 3 weeks in the presence of acetone (as anti-solvent) and then thermally analyzed. In this case, most of the ASDS03 solid was dried on filter paper at RT for up to 2 h and the recovered material was then analyzed by XRPD. The results showed that the material had converted to Form S14 (or a form similar to and / or isostructural to Form S14) ( Fig.35 ). TG / DSC analysis of this material ( Fig.36 ) led to its assignment as a mixed solvate with acetone and water. Therefore, the first endothermic event indicates a desolvation event, where T 起始 =42.8 °C and a mass loss of 3.888% (attributable to 0.25 acetone molecules, corresponding to 3.07% of theoretical mass). The second endothermic event indicates another desolvation event, where T 起始 =103.6°C and a mass loss of 1.982% (attributable to 0.5 water molecules, corresponding to 2.08% of theoretical mass). In addition, a possible recrystallization event was observed on the DSC trace at about 190°C and finally at about 332°C (T 起始 ). The melting event of this sample is T 起始 Unlike the starting material (NaCDC Form B), this means that Form S14 (or a form similar to and / or isostructurally to Form S14) may be a solvate of another anhydrous form.

[0698] Characterization of Form S5

[0699] Form S5 was obtained from experiments ASDS09 and ASDS12 with MeOH (and acetone as antisolvent) at 25°C or 50°C after diffusion for 12 days, and from experiment ASDS10 with MeOH (and ether as antisolvent) at 25°C after diffusion for 12 days. In addition, Form S5 with additional peaks and preferred orientation was obtained from experiments ASDS11 and ASDS13 with MeOH (and MTBE as antisolvent) at 25°C or 50°C, respectively. HPLC purity of the tested materials indicated high purity, ≥93.3% at 212nm.

[0700] Characterization of Forms S9-a and S9-b

[0701] Form S9-a (with preferred orientation) was obtained from experiment ASDS04 after diffusion with water (and acetonitrile as antisolvent) at 25° C. for 12 days. Form S9-b (with preferred orientation but similar to NaCDC monohydrate) was obtained from experiment ASDS08 after diffusion with the same system solvent / antisolvent at 50° C. for 12 days. The HPLC purity of both materials was good (≥86.9%) at 212 nm.

[0702] In experiments ASDS04 and ASDS08, the precipitate formed in aqueous solution in the presence of acetonitrile (as an antisolvent) was stored at RT for up to 24 days before thermal analysis. In this case, most of the solids from experiments ASDS04 and ASDS08 were dried on filter paper at RT for 1-2 h, and the recovered material was then analyzed by XRPD. The results showed that the material from experiment ASDS04 remained unchanged after storage (but with low crystallinity), while the material from experiment ASDS08 had converted to a form similar to form S9-a (and with low crystallinity) ( Fig.37 The corresponding data for the starting materials obtained from experiments ASDS04 (Table S9-a) and ASDS08 (Table S9-b) are summarized as follows:

[0703] Table S9-a

[0704]

[0705]

[0706]

[0707] Table S9-b

[0708]

[0709]

[0710]

[0711] Based on TG / DSC analysis, the sample from experiment ASDS04 that had been stored for 22 days ( Fig.38 ) was assigned as a solvate or mixed solvate with water or MeCN. Therefore, the first endothermic event indicates a desolvation event, where T 起始 =99.9°C and a mass loss of 8.635% (attributable to 2 water molecules, corresponding to 8.32% of the theoretical mass, or to 1 MeCN molecule, corresponding to 9.01% of the theoretical mass). Finally, a T of about 328°C was observed. 起始 The following melting event.

[0712] Based on TG / DSC analysis, the sample from experiment ASDS08 that had been stored for 23 days ( Fig.39 ) was assigned as a solvate or mixed solvate with water or MeCN. Therefore, the first endothermic event indicates a desolvation event, where T 起始 =94.8°C and a mass loss of 2.298% (attributable to 0.5 water molecules, corresponding to 2.08% of the theoretical mass, or to 0.25 MeCN molecules, corresponding to 2.25% of the theoretical mass). Finally, a T of about 336°C was observed. 起始 The following melting event.

[0713] Characterization of Forms S10 and S11

[0714] Form S10 was obtained from experiment ASDS14 after diffusion with TFE (and EtOAc as anti-solvent) at 25°C for 12 days. Form S11 (or a form similar to and / or isostructural to form S3) was obtained from experiment ASDS18 after diffusion with the same system solvent / anti-solvent at 50°C for 12 days. Both samples were evaporated overnight at 30°C, 21 mbar. The HPLC purity of the material from experiment ASDS14 was 91.4%, while the purity of the material from experiment ASDS18 was reduced to 75.6% (at 212 nm).

[0715] The XRPD spectrum of the material from experiment ASDS14 is shown at Fig.40A and the corresponding data are summarized in Table S10: Table S10

[0716]

[0717]

[0718] The XRPD spectrum of the material from experiment ASDS18 is shown at Fig.50A , and the corresponding data are summarized in Table S11:

[0719] Table S11

[0720]

[0721]

[0722] Based on TG / DSC analysis ( Fig.40B ), the material obtained from experiment ASDS14 was assigned as a solvate or mixed solvate with TFE or EtOAc. Therefore, the first endothermic event indicates a desolvation event, where T 起始=141.3°C and a mass loss of 16% (attributable to 1 TFE molecule, corresponding to 19.44% of theoretical mass, or to 1 EtOAc molecule, corresponding to 17.53% of theoretical mass). 起始 The first melting step was observed at T of about 336 °C. 起始 Possible recrystallization and final melting steps.

[0723] Based on TG / DSC analysis ( Fig.41 ), the material obtained from experiment ASDS18 was assigned to anhydrous form with some residual solvent or physical adsorption of solvent. Therefore, a mass loss of 3.799% was observed on the TG curve, but it was not attributed to a well-defined event. A T loss of about 328 °C was observed. 起始 The following melting event.

[0724] Characterization of Form S12

[0725] Form S12 (as a mixture with an amorphous phase) was obtained from experiment ASDS19 after diffusion with TFE (and MTBE as antisolvent) at 50° C. for 12 days. The HPLC purity of the sample was determined to be 97.1% at 212 nm.

[0726] The precipitate formed in the TFE solution in the presence of MTBE (as anti-solvent) was stored at RT for 22 days before thermal analysis. In this case, most of the material from experiment ASDS19 was dried on filter paper at RT for up to 2 h, and the recovered material was then analyzed by XRPD. The results showed that the material that had been stored for 22 days was converted to form S15 (also identified in experiment RAS36) ( Fig.42 ). Considering that form S12 is obtained as a mixture with an amorphous phase and has a low crystallinity, form S12 is likely to be the same as form S15. The XRPD data from experiment ASDS19 before storage for 22 days are summarized in Table S12, and the XRPD data from experiment ASDS19 after storage for 22 days are summarized in Table S15.

[0727] Table S12

[0728]

[0729] Table S15

[0730]

[0731]

[0732] Based on TG / DSC analysis ( Fig.43), the material from experiment ASDS19 stored for 22 days was assigned to be a solvate with MTBE. Therefore, the first endothermic event indicates desolvation, where T 起始 =80.8°C and a mass loss of 4.448% (attributable to 0.25 MTBE molecules, corresponding to 4.38% of theoretical mass). An inflection point at about 180°C is observed and may indicate recrystallization. Finally, a T of about 332°C is observed. 起始 The following melting event.

[0733] Characterization of Form S13

[0734] Form S13 (showing broad peaks and amorphous tendency) was obtained from experiment ASDS16 after diffusion with TFE (and diisopropyl ether as antisolvent) at 25° C. for 12 days. The HPLC purity of the sample was 92.4% at 212 nm.

[0735] The precipitate formed in the TFE solution in the presence of DIPE (as anti-solvent) was stored at RT for 22 days before thermal analysis. In this case, most of the material obtained from experiment ASDS16 was dried on filter paper at RT for up to 2 h and the recovered material was analyzed by XRPD. The results showed that the material that had been stored for 22 days remained unchanged, yielding a low crystalline phase with some additional peaks or preferred orientation ( Fig.44 ).

[0736] Based on TG / DSC analysis ( Fig.45 ), Form S13 was assigned as a mixed solvate with DIPE and TFE. Therefore, the first endothermic event indicates desolvation, where T 起始 =55.4°C and a mass loss of 2.358% (attributable to 0.125 DIPE molecules, corresponding to 2.47% of theoretical mass). The second endothermic event indicates another desolvation, where T 起始 =148.8°C and a mass loss of 3.804% (attributable to 0.25 TFE molecules, corresponding to 4.86% of theoretical mass). The third exothermic event indicates that 起始 =191.8°C. Finally, a recrystallization event at T = 335°C was observed. 起始 The following melting event.

[0737] Characterization of Form S14

[0738] Form S14 was obtained from two experiments, ASDS17 after diffusion with TFE (and acetone as anti-solvent) at 25°C for 12 days and ASDS21 after diffusion with the same system solvent / anti-solvent at 50°C for 12 days. Both samples were evaporated overnight at 30°C, 21 mbar. The HPLC purity of the material from experiment ASDS17 was 89.3%, while the HPLC purity of the material from experiment ASDS21 was about 70% (212 nm). XRPD analysis of the material obtained from experiment ASDS21 is shown in Fig.46A , and the corresponding data are summarized in Table S14:

[0739] Table S14

[0740]

[0741]

[0742] Based on TG / DSC analysis from experiment ASDS17 ( Fig.46B ), Form S14 was assigned as the solvated form with the first endothermic event indicating desolvation at about 143.7 °C with a mass loss of 15.84% (attributable to 1 TFE molecule, corresponding to 19.44% of theoretical mass). The second event represented a desolvation at 331 °C (T 起始 ) under which a melting event occurs. The mass loss of the desolvation event and T 起始 Similar to those of form S4, but melting T 起始 Differently, this means that Form S14 can be a monosolvate with TFE, but a monosolvate of anhydrous forms other than NaCDC Form B.

[0743] Rapid Cooling

[0744] Ten stock solutions (containing water; H) with 1.5 times the solubility (determined from the solubility study of Example 8) were prepared at RT with stirring at 700 rpm and heating at 40 °C for 1 h. 2 O:THF 1:1v / v; H 2 O:EtOH 1:1v / v; H 2 O:2-PrOH 1:1v / v; H 2 O:MeCN 1:1 v / v; H 2O: acetone 1: 1 v / v; methanol; 2,2,2-trifluoroethanol; MeOH: EtOAc 1: 1 v / v; and MeOH: acetone 1: 1 v / v). The mixture that did not dissolve at 40°C was heated at 50°C with additional stirring time or additional solvent volume. The exact concentration of each stock solution is shown in Table 13. After the above time, the solution was completely dissolved and the hot solution was filtered with a 0.45 μm PTFE filter (or a 0.2 μm nylon filter (in the case of water stock solutions)) and kept at the working temperature.

[0745] After filtration, a determined volume of each solution (finally having 196.91-65.72 mg of NaCDC per experiment) was added to appropriate vials, which were further placed at 25° C. (experiments CL01-10), 5° C. (experiments CL11-19) or -20° C. (experiments CL20-23) for aging for 7 days and checked regularly. After the time had passed, no precipitation occurred and the solutions were vacuum evaporated at 30° C., low pressure (final pressure = 20-21 mbar) for about 18 h (experiments CL01, 02, 05, 06, 10, 11, 13, 14, 15, 16, 19, 20, 22 and 23) or about 41 h (experiments CL03, 04, 08, 09, 12, 17 and 18) or 4.5 days (experiments CL07 and 21) and analyzed by XRPD. Based on the results obtained, some experiments were also analyzed by HPLC or TG / DSC. The results from rapid cooling crystallization (CL) are summarized in Table 14.

[0746] Table 13

[0747]

[0748]

[0749] Table 14

[0750]

[0751]

[0752]

[0753] Am. = amorphous; PO = preferred orientation; pks. = peak

[0754] Based on the XRPD data, most experiments yielded amorphous phase material.A distinct form (Form S5) was identified from most experiments involving MeOH as solvent.

[0755] Characterization of Form S5

[0756] Form S5 with a preferred orientation was obtained from the experiment CL16 in which the remaining solution was cooled at 5°C for 7 days with MeOH and then dried in vacuum; or from the experiments CL10 and CL23 in which the remaining solution was cooled at 25 and -20°C for 7 days with MeOH: acetone 1: 1 v / v and then dried in vacuum. In addition, a mixture of Form S5 with a low crystallinity and an amorphous phase was obtained from the experiments CL19 (vacuum drying after cooling the remaining solution at 5°C for 7 days with MeOH: acetone 1: 1 v / v) and CL22 (vacuum drying after cooling the remaining solution at -20°C for 7 days with MeOH: EtOAc 1: 1 v / v). The HPLC purity of these samples was generally good (≥88.5%) at 212 nm (except for the CL22 experiment, which had a purity of 84.8%).

[0757] Based on TG / DSC analysis from experiment CL16 ( Fig.47 ), Form S5 was assigned as the solvated form with the first endothermic event, indicating that desolvation occurred, where T 起始 =120.3 °C and a mass loss of 5.867% (attributable to 0.5 MeOH molecules, corresponding to 3.59% of theoretical mass). 起始 = A second event (likely a phase transition) at 188.1°C. A T representing a transition at 205°C was observed. 结束 The third event of recrystallization occurs at about 336°C (T 起始 ) were observed under the conditions of

[0758] Forward antisolvent addition

[0759] Three stock solutions (containing water; methanol; and 2,2,2-trifluoroethanol) with 1.5 times solubility (determined by the solubility study of Example 8) were prepared at RT with stirring at 700 rpm and heating at 40°C for 1 hour. Not all mixtures dissolved at 40°C, and some of them were heated at 50°C with additional stirring time or additional volume. The exact concentration of each stock solution is provided in Table 13. After the above time, the solution was completely dissolved, and the hot solution was filtered with a 0.45 μm PTFE filter (or a 0.2 μm nylon filter (in the case of water stock solutions)) and maintained at the working temperature. The appropriate anti-solvent was added in 3 steps at 25°C (500 rpm), with each step separated by about 10 minutes, and the total volume ratio of solvent / anti-solvent was 0.5, 1 and 5, respectively. After the anti-solvent was completely added, the experiment was stirred at 25°C for 1 day, and the experiment that produced solids was harvested and analyzed by XRPD. Finally, the experiment (experiment FAS01,02,03,04) that does not produce solid was stirred (500rpm) for 1 week at 5°C, and checked regularly. After the time lapsed, no precipitation occurred, and the solution was vacuum evaporated at 30°C, low pressure (final pressure = 20-21mbar) for about 18h (experiment FAS01 and 04) or 4.5 days (experiment FAS02 and 03), and analyzed by XRPD. Based on the results obtained, some experiments were also analyzed by HPLC or TG / DSC. The results from the positive anti-solvent addition (FAS) at 25°C are presented in Table 15.

[0760] Table 15

[0761]

[0762]

[0763] Am. = amorphous; lc = low crystallinity; SM = starting material (i.e. NaCDC form B); PO = preferred orientation; pks. = peak

[0764] Based on the XRPD data, all experiments with water (and different anti-solvents) resulted in amorphous phase material. Two different forms (Form S4 and Form S5) were identified from most experiments involving MeOH or TFE as solvents.

[0765] Characterization of Form S4

[0766] Form S4 was obtained from most experiments with TFE: Experiment FAS13 with toluene as antisolvent; Experiment FAS15 with iPrOAc; Experiment FAS17 with MTBE; and Experiment FAS18 with DIPE. All tested materials showed good HPLC purity at 212 nm (≥88.8%, except for Experiment FAS13, which was 69.3%). Form S4 was obtained from experiments with TFE and was designated as its solvated form.

[0767] Characterization of Form S5

[0768] Form S5 was obtained (generally with low crystallinity) from all FAS experiments with MeOH (experiment FAS07 with toluene as antisolvent; experiment FAS08 with EtOAc; experiment FAS09 with MTBE; experiment FAS10 with acetone; experiment FAS11 with MEK; and experiment FAS12 with MeCN). The HPLC purity of the material was good at 212 nm (≥91.3%, except for experiment FAS09, which was 80.3% pure). The XPRD spectrum of the material obtained from experiment FAS08 is shown at Fig.23A , and the corresponding data are summarized in Table S5-B:

[0769] Table S5-B

[0770]

[0771]

[0772] Reverse antisolvent addition

[0773] Three stock solutions (containing water; methanol; and 2,2,2-trifluoroethanol) with 1.5 times solubility (as determined in the solubility study of Example 8) were prepared at RT with stirring at 700 rpm and heating at 40°C for 1 hour. Not all mixtures dissolved at 40°C, and some of them were heated at 50°C with additional stirring time or additional volume. The exact concentration of each stock solution is presented in Table 13. After the above time, the solution was completely dissolved, and the hot solution was filtered with a 0.45 μm PTFE filter (or a 0.2 μm nylon filter (in the case of water stock solutions)) and kept at the working temperature.

[0774] The appropriate volume of antisolvent was added to an HPLC vial or 8 mL flask and equilibrated at 5°C or 25°C, and the hot filtered solution (volume determined for each solution, with about 23 mg of NaCDC per experiment in the end, about 39 mg per experiment if aqueous) was added dropwise into the appropriate vial under stirring (500 rpm), with a volume ratio of 1:10 between stock solution and antisolvent (or about 1:12 if the experiment was with water). All experiments were stirred overnight at 5°C or 25°C, and experiments that produced solids were harvested, air-dried on filter paper, and analyzed by XRPD. The remaining experiments were stirred for another 6 days at 5°C or 25°C and checked regularly. If no precipitation occurs, the solution is dried under vacuum at 30°C, low pressure (final pressure = 20-21 mbar) for about 18 h (experiments RAS01, 04, 07, 10, 13 and 25) or 4.5 days (experiments RAS02, 03, 08 and 09) and analyzed by XRPD. Based on the results obtained, some experiments were also analyzed by HPLC or TG / DSC. The results from reverse anti-solvent addition (RAS) at 5°C or 25°C are summarized in Table 16.

[0775] Table 16

[0776]

[0777]

[0778]

[0779]

[0780] Am. = amorphous; lc = low crystallinity; SM = starting material (ie, NaCDC Form B); PO = preferred orientation; pks. = peak; pp. = precipitate

[0781] Based on the XRPD data, much of the recovered material was in an amorphous phase or, in several cases, obtained as starting material (NaCDC Form B). In addition, seven different forms were identified, namely Form S1 (or similar and / or isomorphous to Form S1), Form S3 (or similar and / or isomorphous to Form S3), Form S4, Form S5, Form S6 (or similar and / or isomorphous to Form S6), Form S13, and Form S15.

[0782] Characterization of Form S1

[0783] Form S1 (or a form similar to and / or isostructural to Form S1) was obtained from Experiments RAS05 and RAS11 (water stock solution and acetone as antisolvent) at 5°C and 25°C, respectively. The HPLC purity of the materials was good (≥94.0%) at 212 nm. The XRPD spectrum of the material from Experiment RAS11 is shown at Fig.24A middle.

[0784] The precipitate formed in the aqueous solution was stored at RT for 2 weeks in the presence of acetone (as anti-solvent) and then subjected to thermal analysis. In this case, most of the material obtained from experiment RAS11 was dried on filter paper for 1-2 h at RT and the recovered material was then analyzed by XRPD. The results showed that the stored material had a high tendency to amorphization with several peaks (some of which are similar to and / or isomorphic to Form S1) ( Fig.48 ).

[0785] Based on TG / DSC analysis ( Fig.49 ), the material from experiment RAS11 that had been stored for 2 weeks was assigned to a mixed solvate with acetone and water. Therefore, the first endothermic event indicated desolvation, where T 起始 =41.9 °C and a mass loss of 5.356% (attributable to 0.5 acetone molecules, corresponding to 6.14% of theoretical mass). The second endothermic event indicates another desolvation, where T 起始 =107.2°C and a mass loss of 1.237% (attributable to 0.25 water molecules, corresponding to 1.04% of theoretical mass). A recrystallization event was observed at about 198.4°C and finally at about 327°C (T 起始 ). The melting event of this sample is T 起始 Unlike the starting material (NaCDC Form B), this means that the form may be a solvate of another possible anhydrous form.

[0786] Characterization of Form S3

[0787] Form S3 (or a form similar to and / or isostructural to Form S3) was obtained from Experiment RAS34 (TFE stock solution and iPrOAc as antisolvent) at 25°C. The HPLC purity of the material was 82.3% at 212 nm. The XRPD spectrum of the material obtained from Experiment RAS34 is shown at Fig.50A middle.

[0788] The precipitate formed in the TFE solution in the presence of iPrOAC (as an antisolvent) was stored at RT for 2 weeks before thermal analysis. In this case, most of the material from Experiment RAS34 was dried on filter paper at RT for 1-2 h, and the recovered material was then analyzed by XRPD. The results showed that the stored material from Experiment RAS34 remained unchanged and was in Form S3 (or a form similar to and / or isostructural to Form S3).

[0789] Based on TG / DSC analysis ( Fig.50B ), the material obtained from experiment RAS34 that had been stored for 2 weeks was assigned to be a solvate with TFE or iPrOAc. Therefore, the first endothermic event indicates desolvation, where T 起始 =52.3 °C and a mass loss of 1.323% (attributable to 0.0625 TFE or iPrOAc molecules, corresponding to 1.21% or 1.23% of theoretical mass, respectively), probably residual solvent. The second exothermic event indicates a recrystallization event and is observed at about 195 °C. Finally, at about 336 °C (T 起始 ) were observed under the conditions of

[0790] Characterization of Form S4

[0791] Form S4 was obtained from four experiments, all using TFE stock solutions: Experiment RAS28 (with low crystallinity; nBuOAc as antisolvent at 5°C), Experiment RAS29 (with low crystallinity and extra peaks; MTBE as antisolvent at 5°C), Experiment RAS30 (with extra peaks; DIPE as antisolvent at 5°C), and Experiment RAS32 (toluene as antisolvent at 25°C). The material had good HPLC purity (≥89.4%) at 212 nm.

[0792] Characterization of Form S5

[0793] Form S5 was obtained from most experiments with MeOH stock solution and different antisolvents: experiments RAS14 and RAS20 with EtOAc at 5 and 25°C; experiments RAS15 and RAS21 at 5 and 25°C; experiments RAS16 and RAS22 with acetone at 5 and 25°C; experiments RAS17 and RAS23 with MEK at 5 and 25°C; experiments RAS18 and RAS24 with MeCN at 5 and 25°C; and experiment RAS19 with toluene at 25°C. In some cases, Form S5 was obtained with low crystallinity (i.e., in experiments RAS14, 16, 18, 24). The HPLC purity of the materials was good (≥87.3%) at 212 nm.

[0794] Characterization of Form S6

[0795] Form S6 (or a form similar to and / or isostructural to Form S6) with a preferred orientation was obtained from Experimental RAS33 (TFE stock solution and EtOAc as antisolvent) at 25°C. The HPLC purity of the material was 96.1% at 212 nm. The XRPD spectrum of the material from Experimental RAS33 is shown at Fig.50A , and the corresponding data are summarized in Table S6:

[0796] Table S6

[0797]

[0798]

[0799] The precipitate formed in the TFE solution was stored at RT for 2 weeks in the presence of EtOAc (as anti-solvent) and then subjected to thermal analysis. In this case, most of the material obtained from Experiment RAS33 was dried on filter paper at RT for 1-2 h and the recovered material was then analyzed by XRPD. The results showed that the material from Experiment RAS33 that had been stored for 2 weeks was converted to Form S1 (or a form similar to and / or isostructural to Form S1) ( Fig.51 ).

[0800] Based on TG / DSC analysis ( Fig.52 ), the material from experiment RAS33 that had been stored for 2 weeks was assigned to be a solvate with EtOAc. Therefore, the first endothermic event indicated desolvation, where T 起始 =88.6°C and a mass loss of 2.436% (attributable to 0.125 EtOAc molecules, corresponding to 2.191% of theoretical mass). 起始 ) were observed under the conditions of

[0801] Characterization of Form S13

[0802] Form S13 (with additional peaks) was obtained from experiment RAS37 with TFE (and DIPE as antisolvent) at 25°C. The HPLC purity of the sample was 81.7% at 212 nm. XRPD analysis of the material obtained from experiment RAS37 is shown in Fig.53 , and the corresponding data are summarized in Table S13:

[0803] Table S13

[0804]

[0805] Characterization of Form S15

[0806] Form S15 was obtained from experiment RAS36 with TFE (and MTBE as antisolvent) at 25° C. The HPLC purity of the sample was 86% at 212 nm.

[0807] The precipitate formed in the TFE solution was stored at RT for 2 weeks in the presence of MTBE (as anti-solvent) and then subjected to thermal analysis. In this case, most of the material obtained from Experiment RAS36 that had been stored for 2 weeks was dried on filter paper at RT for 1-2 h and the recovered material was analyzed by XRPD. The results showed that the material obtained from Experiment RAS36 that had been stored for 2 weeks was converted to Form S14 (or a form similar to and / or isomorphic to Form S14) or to a mixture of Form S15 and another form ( Fig.54A ).

[0808] Based on TG / DSC analysis ( Fig.54B ), the material obtained from experiment RAS36 that had been stored for 2 weeks was assigned to a mixed solvate with MTBE and TFE. Therefore, the first extensive endothermic event indicated that 起始 = desolvation at 87.8°C. The second event indicates that 起始 = Exsolution at 125.4°C. The combined two processes are assigned a mass loss of 4.09%. The inflection point at about 185°C may indicate recrystallization. Finally, a T of about 334°C is observed. 起始 The following melting event.

[0809] Although we have described several embodiments of the present invention, it is apparent that our basic examples can be altered to provide other embodiments utilizing the compounds and methods of the present invention. It should be understood, therefore, that the scope of the invention is defined by the appended claims rather than by the specific embodiments presented by way of example.

Claims

1. A crystalline solid form of sodium chenodeoxycholate, wherein the solid form is anhydrous and is characterized by one or more peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2θ.

2. The solid form of claim 1, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 6.75, about 8.14, about 9.79, about 14.02, about 16.10, and about 18.63 degrees 2-theta.

3. The solid form of claim 2, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the following positions:

4. The solid form of any one of claims 1-3, wherein the solid form is characterized by one or more of the following: (i) an XRPD pattern substantially similar to that depicted in FIG5 ; (ii) DSC graph showing no thermal events from room temperature to about 288°C; (iii) a DSC graph substantially similar to that depicted in FIG6 ; (iv) a TGA graph showing a weight loss of <0.1% up to 150°C; or (v) A TGA graph substantially similar to that depicted in FIG. 7 .

5. A crystalline solid form of sodium chenodeoxycholate prepared by a method comprising the steps of: providing a mixture of chenodeoxycholic acid in n-butanol; adding aqueous sodium hydroxide to the mixture; heating the mixture (e.g., to azeotropic reflux); and removing the solvent to provide the crystalline solid form of sodium chenodeoxycholate.

6. A crystalline solid form of sodium chenodeoxycholate, wherein the solid form is a hydrate and is characterized by one or more peaks in its XRPD pattern selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2θ.

7. The solid form of claim 6, wherein the solid form is characterized by peaks in its XRPD pattern selected from those at about 6.07, about 6.55, about 10.72, about 14.64, about 15.06, about 17.58, and about 18.34 degrees 2-theta.

8. The solid form of claim 7, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the following positions:

9. The solid form of any one of claims 6-8, wherein the solid form is characterized by one or more of the following: (i) an XRPD pattern substantially similar to that depicted in FIG1 ; (ii) DSC graph showing water loss starting from slightly above ambient temperature and continuing to about 150°C; (iii) a DSC graph substantially similar to that depicted in FIG2 ; (iv) a TGA graph showing a weight loss of 4.3% up to 150°C; or (v) A TGA graph substantially similar to that depicted in FIG3 .

10. A crystalline solid form of sodium chenodeoxycholate prepared by a process comprising the steps of: providing a mixture of chenodeoxycholic acid in methyl isobutyl ketone; adding aqueous sodium hydroxide to the mixture; heating the mixture (e.g., to azeotropic reflux); and removing the solvent to provide the crystalline solid form of sodium chenodeoxycholate.

11. A crystalline solid form of sodium chenodeoxycholate, wherein the solid form: (i) characterized by one or more peaks in its XRPD pattern selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-theta; (ii) characterized by one or more peaks in its XRPD pattern selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-theta; (iii) characterized by one or more peaks in its XRPD pattern selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-theta; (iv) characterized by one or more peaks in its XRPD pattern selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-theta; (v) characterized by one or more peaks in its XRPD pattern selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-theta; (vi) characterized by one or more peaks in its XRPD pattern selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-theta; (vii) characterized by one or more peaks in its XRPD pattern selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-theta; (viii) characterized by one or more peaks in its XRPD pattern selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-theta; (ix) characterized by one or more peaks in its XRPD pattern selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-theta; (x) characterized by one or more peaks in its XRPD pattern selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-theta; (xi) characterized by one or more peaks in its XRPD pattern selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-theta; or (xii) characterized by one or more peaks in its XRPD pattern selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-theta.

12. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.45, about 5.80, about 7.46, about 9.76, about 12.40, about 14.88, and about 20.02 degrees 2-theta.

13. The solid form of claim 12, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S1-A or Table S1-B.

14. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 7.11, about 7.78, about 9.81, about 12.58, about 12.96, and about 13.54 degrees 2-theta.

15. The solid form of claim 14, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S2.

16. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.00, about 7.56, about 10.56, about 11.45, about 11.93, and about 12.46 degrees 2-theta.

17. The solid form of claim 16, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S3, Table S6, or Table S11.

18. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 7.07, about 7.65, about 9.70, about 13.43, about 15.02, about 16.52, and about 16.96 degrees 2-theta.

19. The solid form of claim 18, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S4.

20. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 7.11, about 8.63, about 12.08, about 12.75, about 13.46, about 14.25, and about 16.68 degrees 2-theta.

21. The solid form of claim 20, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S5.

22. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 8.47, about 9.90, about 14.36, about 15.26, about 17.00, and about 17.72 degrees 2-theta.

23. The solid form of claim 22, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S7.

24. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.10, about 7.00, about 13.52, about 14.23, about 15.46, and about 18.78 degrees 2-theta.

25. The solid form of claim 24, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S9-a.

26. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.47, about 7.48, about 9.82, about 12.66, and about 15.07 degrees 2-theta.

27. The solid form of claim 26, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S9-b.

28. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.13, about 7.01, about 8.69, about 9.11, about 13.55, about 14.91, and about 15.53 degrees 2-theta.

29. The solid form of claim 28, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S10.

30. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 4.82, about 5.22, about 5.89, about 10.81, about 13.00, about 15.00, and about 18.94 degrees 2-theta.

31. The solid form of claim 30, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S12 or Table S15.

32. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 4.95, about 7.53, about 9.85, about 11.55, about 12.12, and about 15.01 degrees 2-theta.

33. The solid form of claim 32, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S13.

34. The solid form of claim 11, wherein the solid form is characterized by one or more peaks in its XRPD pattern selected from those at about 5.15, about 5.50, about 7.05, about 12.04, about 14.90, and about 16.56 degrees 2-theta.

35. The solid form of claim 34, wherein the solid form is characterized by peaks in its XRPD pattern located at substantially all of the positions listed in Table S14.

36. A crystalline solid form of sodium chenodeoxycholate obtainable by the method described herein.

37. A pharmaceutical composition comprising the solid form of any one of claims 1-36 and a pharmaceutically acceptable carrier.

38. The pharmaceutical composition of claim 37, wherein the pharmaceutical composition is a solid.

39. The pharmaceutical composition of claim 37 or 38, wherein the pharmaceutical composition is formulated for oral administration.

40. A pharmaceutical composition prepared by a method comprising the steps of: providing a solid form as described in any one of claims 1-36; and formulating the solid form with a suitable excipient to provide the pharmaceutical composition.

41. A pharmaceutical composition comprising: a first portion comprising a bile acid or a salt thereof, wherein the first portion is configured for immediate release in the colon of a subject; a second portion adjacent to the first portion, the second portion comprising a bile acid or a salt thereof, and wherein the second portion is configured for extended release in the colon of a subject; and a degradable or erodible coating associated with said pharmaceutical composition, wherein at least one of the first part or the second part comprises a solid form as described in any one of claims 1-36.

42. A pharmaceutical composition comprising: a first portion comprising a bile acid or a salt thereof, wherein the first portion is configured for immediate release in the colon of a subject; a second portion adjacent to the first portion, the second portion comprising a bile acid or a salt thereof, and wherein the second portion is configured for extended release in the colon of a subject; and A degradable or erodible coating associated with the pharmaceutical composition, wherein at least one of the first part or the second part comprises a solid form as described in any one of claims 1 to 36, The pharmaceutical composition is prepared by a method comprising the following steps: Providing a solid form as described in any one of claims 1-36; and The solid form is formulated with suitable excipients to provide the pharmaceutical composition.

43. The pharmaceutical composition of claim 41 or 42, wherein the pharmaceutical composition is a tablet.

44. The pharmaceutical composition of any one of claims 41-43, wherein the bile acid or salt thereof in the first part and the second part is chenodeoxycholic acid or a salt thereof.

45. The pharmaceutical composition of claim 44, wherein the first part and the second part comprise a solid form as described in any one of embodiments 1-36.

46. ​​The pharmaceutical composition of any one of claims 41-45, wherein the coating is or comprises Eudragit S100.

47. A method comprising administering to a subject in need thereof the solid form of any one of claims 1-36 or the pharmaceutical composition of any one of claims 37-46.

48. The method of claim 47, comprising orally administering a solid form of any one of claims 1-36 or a pharmaceutical composition of any one of claims 37-46.

49. A method of treating a disease, disorder or condition comprising administering to a subject in need thereof a solid form of any one of claims 1-36 or a pharmaceutical composition of any one of claims 37-46.

50. The method of any one of claims 47-49, wherein the subject suffers from a gastrointestinal disease, disorder or condition.

51. The method of any one of claims 47-49, wherein the subject suffers from constipation.

52. The method of any one of claims 47-49, wherein the subject suffers from irritable bowel syndrome with constipation (IBS-C).

53. A method for preparing a solid form as described in any one of claims 1-10, wherein the method comprises the following steps: Provides chenodeoxycholic acid; as well as Contact chenodeoxycholic acid with a suitable base in a suitable solvent To provide the solid form.

54. A process as claimed in claim 53, wherein the suitable base is sodium hydroxide.

55. A process as claimed in claim 53 or 54, wherein the suitable solvent is selected from methyl isobutyl ketone, n-butanol and water.

56. A method for preparing a pharmaceutical composition as described in any one of claims 37-46, wherein the method comprises the following steps: Providing a solid form as described in any one of claims 1-36; as well as The solid form is formulated with suitable excipients. To provide the pharmaceutical composition.